Resin composition, resin sheet, prepreg and printed circuit board

By using a resin composition containing specific maleimide compounds, polyphenylene ether compounds and block copolymers, the problems of unstable dielectric constant and poor dielectric loss angle tangent of the printed circuit board insulating layer in thin film and high frequency environments are solved, and excellent low dielectric characteristics and peel strength are achieved.

CN115003716BActive Publication Date: 2025-04-11MITSUBISHI GAS CHEM CO INC +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180009886.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-25
Filing Date
2021-01-20
Publication Date
2025-04-11
Estimated Expiration
2041-01-20

AI Technical Summary

Technical Problem

The insulating layer of the existing printed circuit board has problems such as unstable dielectric constant, poor tangent of dielectric loss angle and insufficient peel strength in the thin film and high frequency environment.

Method used

A resin composition is used, which contains a maleimide compound having an aromatic ring on the main skeleton and having a relative dielectric constant of less than 2.7 at 10 GHz when hardened alone, a polyphenylene ether compound having a number average molecular weight of 1000 or more and a block copolymer having a styrene framework.

Benefits of technology

Excellent low dielectric constant, low dielectric loss angle tangency, flexibility and peel strength are achieved, and filming can be thinned and high-frequency signal loss can be reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115003716B_ABST
    Figure CN115003716B_ABST
Patent Text Reader

Abstract

The present invention provides a resin composition, resin sheet, prepreg and printed circuit board that can obtain excellent low dielectric constant, low dielectric loss tangent, flexibility and peel strength. The resin composition of the present invention is characterized in that it contains: a maleimide compound (A) with a relative dielectric constant of less than 2.7, a polyphenylene ether compound (B) with a number average molecular weight of more than 1000 and less than 7000 shown in the following general formula (1), and a block copolymer (C) having a styrene skeleton; in the above general formula (1), X represents an aryl group, ‑(Y‑О)n2‑ represents a polyphenylene ether portion, R1, R2, and R3 each independently represent a hydrogen atom, an alkyl group, an alkenyl group or an alkynyl group, n2 represents an integer of 1 to 100, n1 represents an integer of 1 to 6, and n3 represents an integer of 1 to 4.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a resin sheet, a prepreg and a printed circuit board using the resin composition. [Background technology]

[0002] In recent years, it is widely used in the printed circuit boards of electronic machines, communication machines, personal computers, etc., towards high density, high integration, and thinness. Along with this, the insulating layer of the printed circuit board requires lower dielectric constant (permittivity, permittivity), low dielectric loss tangent (dissipation factor), and filmization. In the past, various studies have been conducted on the resin composition used for the insulating layer. For example, in patent document 1, a resin composition is recorded, containing: maleimide compound (A), cyanate compound (F), polyphenylene ether compound (B) with a number average molecular weight of more than 1000 and less than 7000 with a specific structure, and a block copolymer (C) with a styrene skeleton. According to the resin composition, low dielectric constant, low dielectric loss tangent, and low thermal expansion can be achieved simultaneously, and a uniform hardener can be obtained.

[0003] Prior art literature

[0004] [Patent Document]

[0005] [Patent Document 1] International Publication No. 2019 / 230945 [Summary of the invention]

[0006] [Technical problem to be solved by the invention]

[0007] However, in the past printed circuit boards, for example, prepregs impregnated with resin in glass fibers were more often used for insulating layers. The resin composition described in Patent Document 1 should also be in the prepregs. The prepregs may have a certain strength due to the glass fibers, but a thickness thinner than that of the glass fibers cannot be obtained. Therefore, there is an insufficient problem in the filmization in recent years. In addition, in the case of prepregs, since the dielectric constants and dielectric loss tangents of glass fibers and resins are different, the characteristics of the insulating layer become uneven, and the dielectric constant and dielectric loss tangent of glass fibers are larger than those of resins, so there is also a problem of difficulty in further seeking low dielectric constant and low dielectric loss tangent. In addition, with the high frequency of electronic signals in recent years, there is a problem that if the dielectric constant of the insulating layer is unstable due to the skin effect, the high-frequency signal loss becomes larger, and it is difficult to obtain sufficient characteristics.

[0008] In addition, if the insulating layer is formed by resin instead of glass fiber, it is possible to achieve thin film, low dielectric constant, low dielectric loss tangent, and low high-frequency signal loss. However, the resin compositions in the past have the following problems: insufficient flexibility cannot be obtained and poor molding occurs, or sufficient peel strength cannot be obtained.

[0009] The present invention is completed in view of such problems, and the first purpose is to provide a resin composition that can obtain excellent low dielectric constant, low dielectric loss tangent, flexibility and peel strength, and can be made into a thin film and can reduce high-frequency signal loss; and to provide a resin sheet and a printed circuit board using the resin composition.

[0010] Furthermore, a second object is to provide a prepreg which can obtain excellent moldability, low dielectric constant, low dielectric loss tangent, and peel strength.

[0011] [Technical means]

[0012] The present inventors have discovered that the above-mentioned problems can be solved by using a resin composition comprising a maleimide compound (A) having an aromatic ring in its main skeleton and having a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, a specific polyphenylene ether compound (B), and a block copolymer (C) having a styrene skeleton in combination, thereby completing the present invention.

[0013] That is, the present invention is as follows.

[0014] [1] A resin composition comprising:

[0015] A maleimide compound (A) having an aromatic ring as the main skeleton and a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, a polyphenylene ether compound (B) having a number average molecular weight of 1000 to 7000 represented by the following general formula (1), and a block copolymer (C) having a styrene skeleton;

[0016] [Chemistry 1]

[0017]

[0018] In the above general formula (1), X represents an aromatic group, -(Y-О)n2- represents a polyphenylene ether portion, R1, R2, and R3 each independently represent a hydrogen atom, an alkyl group, an alkenyl group, or an alkynyl group, n2 represents an integer from 1 to 100, n1 represents an integer from 1 to 6, and n3 represents an integer from 1 to 4.

[0019] [2] The resin composition according to [1], wherein the maleimide compound (A) is at least one selected from the group consisting of a compound represented by the following general formula (6) and a compound represented by the following general formula (22);

[0020] [Chemistry 2]

[0021]

[0022] In the above general formula (6), n6 represents an integer greater than 1;

[0023] [Chemistry 3]

[0024]

[0025] In the above general formula (22), R M1 , R M2 , R M3 , R M4 Each independently represents a hydrogen atom or an organic group; R M5 and R M6 Each independently represents a hydrogen atom or an alkyl group; Ar M represents a divalent aromatic group; A is a 4- to 6-membered alicyclic group; R M7 and R M8 Each independently represents an alkyl group; mx is 1 or 2, lx is 0 or 1; R M9 and R M10 Each independently represents a hydrogen atom or an alkyl group; R M11 , R M12 , R M13 and R M14 Each independently represents a hydrogen atom or an organic group; and nx represents an integer of 0 or more and 20 or less.

[0026] [3] The resin composition as described in [1], wherein the block copolymer (C) having a styrene skeleton contains at least one selected from the group consisting of styrene-butadiene block copolymers, styrene-isoprene block copolymers, styrene-hydrogenated butadiene block copolymers, styrene-hydrogenated isoprene copolymers and styrene-hydrogenated (isoprene / butadiene) copolymers.

[0027] [4] The resin composition according to [1], further comprising a maleimide compound (D) other than the maleimide compound (A).

[0028] [5] The resin composition according to [4], wherein the maleimide compound (D) comprises at least one selected from the group consisting of the following general formulas (2), (3), (4) and (5);

[0029] [Chemistry 4]

[0030]

[0031] In the above general formula (2), R 41 , R42 Each independently represents a hydrogen atom or a methyl group, and n4 represents an integer greater than 1;

[0032] [Chemistry 5]

[0033]

[0034] In the above general formula (3), R 501 , R 502 , R 503 , R 504 , R 505 , R 506 , R 507 , R 508 , R 509 , R 510 , R 511 , R 512 Each independently represents a hydrogen atom, an alkyl group having 1 to 8 carbon atoms, or a phenyl group, and n5 represents an integer of 1 to 10;

[0035] [Chemistry 6]

[0036]

[0037] In the above general formula (4), R 61 , R 62 , R 63 , R 64 Each independently represents a hydrogen atom, a methyl group or an ethyl group, and R 71 , R 72 each independently represents a hydrogen atom or a methyl group;

[0038] [Chemistry 7]

[0039]

[0040] In the above general formula (5), R 81 , R 82 Each independently represents a hydrogen atom, a methyl group or an ethyl group.

[0041] [6] The resin composition according to [1], further comprising a flame retardant (E).

[0042] [7] The resin composition according to [1], further comprising a cyanate ester compound (F).

[0043] [8] A resin sheet comprising: a support, and a layer formed from the resin composition described in [1] and disposed on a surface of the support.

[0044] [9] A prepreg comprising: a substrate, and the resin composition described in [1] impregnated or coated on the substrate.

[0045]

[10] A printed circuit board comprising an insulating layer and a conductive layer disposed on a surface of the insulating layer, wherein the insulating layer comprises a layer formed from the resin composition described in [1].

[0046] [Effects of the invention]

[0047] The resin composition, resin sheet and printed circuit board of the present invention can obtain excellent low dielectric constant, low dielectric loss tangent, flexibility, peel strength, can be thin-filmed, and can reduce high-frequency signal loss. In addition, if used as a prepreg, excellent formability, low dielectric constant, low dielectric loss tangent, and peel strength can be obtained. Thus, industrial practicability is extremely high. [Specific implementation method]

[0048] Hereinafter, a mode for carrying out the present invention (hereinafter referred to as "the present embodiment") will be described in detail, but the present invention is not limited thereto and various modifications can be made without departing from the gist of the invention.

[0049] [Resin composition]

[0050] The resin composition of this embodiment contains: a maleimide compound (A) having an aromatic ring in its main skeleton and a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, a polyphenylene ether compound (B) having a number average molecular weight of greater than 1000 and less than 7000 represented by the following general formula (1), and a block copolymer (C) having a styrene skeleton.

[0051] [Chemistry 8]

[0052]

[0053] In the above general formula (1), X represents an aromatic group, -(Y-О)n2- represents a polyphenylene ether portion, R1, R2, and R3 each independently represent a hydrogen atom, an alkyl group, an alkenyl group, or an alkynyl group, n2 represents an integer from 1 to 100, n1 represents an integer from 1 to 6, and n3 represents an integer from 1 to 4.

[0054] [Maleimide compound (A)]

[0055] The maleimide compound (A) of the present embodiment is a compound having one or more maleimide groups in the molecule, and the relative dielectric constant at 10GHz is less than 2.7 when cured alone. The resin composition of the present embodiment, by containing the maleimide compound (A), can obtain excellent low dielectric constant, low dielectric loss tangent, and peel strength. The maleimide compound (A), for example, preferably contains at least one or more of the group consisting of the compound represented by the following general formula (6) and the compound represented by the following general formula (22).

[0056] [Chemistry 9]

[0057]

[0058] In the above general formula (6), n6 represents an integer greater than or equal to 1. The compound (A) represented by the general formula (6) may contain two or more compounds in which n6 is different.

[0059] [Chemistry 10]

[0060]

[0061] In the above general formula (22), R M1 , R M2 , R M3 , R M4 Each independently represents a hydrogen atom or an organic group. M5 and R M6 Each independently represents a hydrogen atom or an alkyl group. M represents a divalent aromatic group. A is a 4- to 6-membered alicyclic group; R M7 and R M8 Each independently represents an alkyl group. mx is 1 or 2, and lx is 0 or 1. M9 and R M10 Each independently represents a hydrogen atom or an alkyl group. M11 , R M12 , R M13 and R M14 Each independently represents a hydrogen atom or an organic group. nx represents an integer of 0 or more and 20 or less.

[0062] The compound (A) represented by the general formula (22) may contain two or more compounds in which nx are different.

[0063] R in the general formula (22) M1 , R M2 , R M3 , and R M4Each independently represents a hydrogen atom or an organic group. The organic group herein is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group. M1 and R M3 Preferably, each independently is an alkyl group, R M2 and R M4 Preferred is a hydrogen atom.

[0064] R M5 and R M6 Each independently represents a hydrogen atom or an alkyl group, preferably an alkyl group. The alkyl group herein is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group.

[0065] Ar M Ar represents a divalent aromatic group, preferably phenylene, naphthalene diyl, phenanthrene diyl, anthracene diyl, more preferably phenylene, and further preferably m-phenylene. M It may have a substituent, and the substituent is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group. M Preferably, there is no substituent.

[0066] A is a 4- to 6-membered alicyclic group, more preferably a 5-membered alicyclic group (preferably a group that combines with a benzene ring to form an indane ring). M7 and R M8 Each independently represents an alkyl group, preferably an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 3 carbon atoms, and particularly preferably a methyl group. mx is 1 or 2, preferably 2. lx is 0 or 1, preferably 1.

[0067] R M9 and R M10 Each independently represents a hydrogen atom or an alkyl group, preferably an alkyl group. The alkyl group herein is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group.

[0068] R M11 , R M12 , R M13 and R M14 Each independently represents a hydrogen atom or an organic group. The organic group herein is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group. M12 and R M13 Preferably, each independently is an alkyl group, RM11 and R M14 Preferred is a hydrogen atom.

[0069] nx is an integer greater than or equal to 0 and less than or equal to 20. nx may also be an integer less than or equal to 10. In addition, the resin composition of the present embodiment is a maleimide compound (A) represented by the general formula (22), and when it contains a compound in which nx is 0, in addition to the compound in which nx is 0, it contains at least one compound other than the compound in which nx is 0, but it may also contain two or more compounds other than the compound in which nx is 0. When it does not contain a compound in which nx is 0, it may contain at least only one compound in which nx has a different value, or it may contain two or more compounds in which nx has different values. In the case of containing two or more, the average value (average number of repeating units) n of nx of the maleimide compound (A) represented by the general formula (22) in the resin composition is preferably 0.95 or more, more preferably 0.98 or more, further preferably 1.0 or more, and further preferably 1.1 or more, and further preferably 10.0 or less, more preferably 8.0 or less, further preferably 7.0 or less, and further preferably 6.0 or less, in order to form a low melting point (low softening point) and a low melt viscosity, and excellent handling properties. The same applies to the formulas (26) and (27) described later.

[0070] The compound represented by the general formula (22) is preferably a compound represented by the following general formula (26).

[0071] [Chemistry 11]

[0072]

[0073] In general formula (26), R M21 , R M22 , R M23 and R M24 Each independently represents a hydrogen atom or an organic group. M25 and R M26 Each independently represents a hydrogen atom or an alkyl group. M27 , R M28 , R M29 and R M30 Each independently represents a hydrogen atom or an organic group. M31 and R M32 Each independently represents a hydrogen atom or an alkyl group. M33 , R M34 , R M35 and R M36 Each independently represents a hydrogen atom or an organic group. M37 , R M38 , R M39 Each independently represents a hydrogen atom or an alkyl group. nx represents an integer of 0 or more and 20 or less.

[0074] In general formula (26), R M21 , R M22 , R M23 and R M24 Each independently represents a hydrogen atom or an organic group. The organic group herein is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group. M21 and R M23 Preferably, it is an alkyl group, R M22 and R M24 Preferred is a hydrogen atom.

[0075] R M25 and R M26 Each independently represents a hydrogen atom or an alkyl group, preferably an alkyl group. The alkyl group herein is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group.

[0076] R M27 , R M28 , R M29 and R M30 Each independently represents a hydrogen atom or an organic group, preferably a hydrogen atom. The organic group herein is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, a butyl group, and particularly preferably a methyl group.

[0077] R M31 and R M32 Each independently represents a hydrogen atom or an alkyl group, preferably an alkyl group. The alkyl group herein is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group.

[0078] R M33 , R M34 , R M35 and R M36 Each independently represents a hydrogen atom or an organic group. The organic group herein is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group.

[0079] R M33 and R M36 Preferably, it is a hydrogen atom, R M34 and R M35 Preferably it is an alkyl group.

[0080] R M37 , R M38 , R M39Each independently represents a hydrogen atom or an alkyl group, preferably an alkyl group. The alkyl group herein is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group.

[0081] nx represents an integer greater than or equal to 0 and less than or equal to 20. nx may be an integer less than or equal to 10.

[0082] The compound represented by general formula (26) is preferably a compound represented by general formula (27).

[0083] [Chemistry 12]

[0084]

[0085] In general formula (27), nx represents an integer greater than or equal to 0 and less than or equal to 20.

[0086] The molecular weight of the compound (A) shown in the general formula (22) is preferably 500 or more, more preferably 600 or more, and further preferably 700 or more. By making the molecular weight above the aforementioned lower limit, there is a tendency to further improve dielectric properties (low dielectric properties) and low water absorption. In addition, the molecular weight of the compound (A) shown in the general formula (22) is preferably 10000 or less, more preferably 9000 or less, further preferably 7000 or less, further preferably 5000 or less, and further preferably 4000 or less. By making the molecular weight below the aforementioned upper limit, there is a tendency to further improve heat resistance and operability.

[0087] In addition, the compound (A) represented by the general formula (22) used in the present embodiment preferably has a high heat resistance in its cured product. The cured product of the compound (A) represented by the general formula (22) used in the present embodiment preferably has a glass transition temperature of 180°C or more, more preferably 200°C or more, and further preferably 230°C or more, as measured in accordance with the JIS C6481 dynamic viscoelasticity test. By making the glass transition temperature above the aforementioned lower limit, a cured product with better heat resistance can be obtained. In addition, the upper limit of the aforementioned glass transition temperature is actually below 400°C.

[0088] In addition, the compound (A) shown in the general formula (22) used in the present embodiment is preferably such that the dielectric properties of its hardened material are excellent. For example, the hardened material of the compound (A) shown in the general formula (22) used in the present embodiment is preferably a relative dielectric constant of less than 2.7 at 10 GHz measured by the cavity perturbation method, and more preferably less than 2.6. In addition, the lower limit of the aforementioned dielectric constant is, for example, actually greater than 2.0. In addition, the hardened material of the compound (A) shown in the formula (22) used in the present embodiment is preferably a relative dielectric loss tangent (Df) of less than 0.01 at 10 GHz measured by the cavity perturbation method, and more preferably less than 0.007. In addition, the lower limit of the aforementioned dielectric loss tangent is, for example, actually greater than 0.0001.

[0089] In addition, the resin combination of the present embodiment, the content of the compound (A) shown in the general formula (22) is preferably more than 1% by mass, more preferably more than 5% by mass, relative to the total amount of resin solids. By making content more than the aforementioned lower limit, there is a tendency to further improve heat resistance. In addition, the upper limit of the content of the compound (A) shown in the general formula (22) is preferably less than 90% by mass of the resin solids in the resin combination, more preferably less than 60% by mass, further more preferably less than 40% by mass, and also less than 30% by mass. By making content less than the aforementioned upper limit, there is a tendency to further improve low water absorption.

[0090] The resin composition of the present embodiment may contain only one compound (A) represented by the general formula (22), or may contain two or more compounds. When containing two or more compounds, the total amount is preferably within the above range.

[0091] The maleimide compound (A) used in the present embodiment may also use commercially available products. For example, the maleimide compound represented by general formula (6) may appropriately use "MIR-5000" manufactured by Nippon Kayaku Co., Ltd.". For example, the maleimide compound represented by general formula (22) may appropriately use "X9-450" or "X9-470" manufactured by DIC Co., Ltd.

[0092] When the resin solid content in the resin composition is set to 100 parts by mass, the lower limit of the content of the maleimide compound (A) of the resin composition of the present embodiment is preferably more than 1 part by mass, more preferably more than 5 parts by mass; its upper limit is preferably less than 90 parts by mass, more preferably less than 60 parts by mass, further preferably less than 40 parts by mass, and also less than 30 parts by mass. By making it in such a range, there is a tendency to effectively achieve low dielectric constant, low dielectric loss tangent and good flexibility.

[0093] The maleimide compound (A) may be used alone or in combination of two or more. When two or more are used, it is preferred that the total amount is within the above range. Here, "resin solid content in the resin composition", unless otherwise specified, refers to the component in the resin composition excluding the solvent; 100 parts by mass of the resin solid content means that the total amount of the component in the resin composition excluding the solvent is 100 parts by mass.

[0094] [Polyphenylene ether compound (B)]

[0095] The polyphenylene ether compound (B) of the present embodiment is the compound shown in the general formula (1). The resin composition of the present embodiment is by containing the polyphenylene ether compound (B) with such a structure, and excellent low dielectric constant and low dielectric loss tangent can be obtained, and a uniform hardener can be obtained. In addition, the present embodiment, by using the maleimide compound (A) and the polyphenylene ether compound (B) shown in the general formula (22), can achieve more excellent dielectric properties compared with the situation of the maleimide compound and the polyphenylene ether compound (B) used in the past. The polyphenylene ether compound (B) shown in the general formula (1) used in the present embodiment, the number average molecular weight is more than 1000 and less than 7000. By making the number average molecular weight less than 7000, the fluidity during molding can be ensured. In addition, by making the number average molecular weight more than 1000, the excellent dielectric properties (low dielectric constant, low dielectric loss tangent) and heat resistance that the polyphenylene ether resin itself has can be obtained. In order to obtain better fluidity, heat resistance, and dielectric properties, the number average molecular weight of the polyphenylene ether compound (B) may be 1100 to 5000, preferably 4500 or less, and more preferably 3000 or less. The number average molecular weight is measured using a gel permeation chromatograph according to a predetermined method.

[0096] The polyphenylene ether compound (B) represented by the general formula (1) used in this embodiment preferably has a minimum melt viscosity of 50,000 Pa·s or less. By setting the minimum melt viscosity to 50,000 Pa·s or less, fluidity can be ensured and multilayer molding can be achieved. The lower limit of the minimum melt viscosity is not particularly limited, and for example, it can be 1,000 Pa·s or more.

[0097] The polyphenylene ether compound (B) represented by the general formula (1) is preferably a polymer containing a structural unit represented by the following general formula (7).

[0098] [Chemistry 13]

[0099]

[0100] In general formula (7), R 901 , R902 , R 903 , R 904 , which may be the same or different, represent an alkyl group, an aryl group, a halogen atom or a hydrogen atom having 6 or less carbon atoms.

[0101] The aforementioned polymer may further contain at least one structural unit selected from the group consisting of structural units represented by general formula (8) and general formula (9).

[0102] [Chemistry 14]

[0103]

[0104] In general formula (8), R 905 , R 906 , R 907 , R 911 , R 912 , which may be the same or different, represent an alkyl group with a carbon number of 6 or less or a phenyl group. 908 , R 909 , R 910 , each independently represents a hydrogen atom, an alkyl group having 6 or less carbon atoms, or a phenyl group.

[0105] [Chemistry 15]

[0106]

[0107] In general formula (9), R 913 , R 914 , R 915 , R 916 , R 917 , R 918 , R 919 , R 920 , which may be the same or different, represent a hydrogen atom, an alkyl group having 6 or less carbon atoms, or a phenyl group. -A- is a linear, branched, or cyclic divalent hydrocarbon group having 20 or less carbon atoms.

[0108] In relation to the general formula (1), preferably the general formulas (8), (9) and (10) are -(YO)- of the general formula (1). -(YO)- is a repeating unit having n2 as a number (1 to 100).

[0109] In general formula (1), X represents an aryl group (aromatic group), -(YO)n2- represents a part of polyphenylene ether, R1, R2, and R3 each independently represent a hydrogen atom, an alkyl group, an alkenyl group, or an alkynyl group, n2 represents an integer of 1 to 100, n1 represents an integer of 1 to 6, and n3 represents an integer of 1 to 4. Preferably, n1 is an integer of 1 to 4, more preferably, n1 is 1 or 2, and ideally, n1 is 1. In addition, preferably, n3 is an integer of 1 to 3, more preferably, n3 is 1 or 2, and ideally, n3 is 2.

[0110] For the aryl group in X of the general formula (1), an aromatic hydrocarbon group can be used. Specifically, a group obtained by removing n3 hydrogen atoms from a ring structure selected from a benzene ring structure, a biphenyl structure, an indenyl ring structure and a naphthalene ring structure (for example, a phenyl group, a biphenyl group, an indenyl group and a naphthyl group) can be used, and preferably a biphenyl group is used. Here, the aryl group may also contain a diphenyl ether group bonded to the above-mentioned aryl group via an oxygen atom, a benzophenone group bonded to a carbonyl group, a 2,2-diphenylpropane group bonded to an alkylene group, and the like. In addition, the aryl group may also be substituted by a general substituent such as an alkyl group (suitably an alkyl group having 1 to 6 carbon atoms, especially a methyl group), an alkenyl group, an alkynyl group or a halogen atom. However, the aforementioned "aryl group" is substituted into the polyphenylene ether portion via an oxygen atom, so the limit of the number of general substituents depends on the number of polyphenylene ether portions.

[0111] The polyphenylene ether compound (B) is particularly preferably a polyphenylene ether having a structure represented by the following general formula (10).

[0112] [Chemistry 16]

[0113]

[0114] In the general formula (10), X is an aryl group (aromatic group), -(YO)n2- each represents a polyphenylene ether moiety, and n2 each represents an integer of 1 to 100.

[0115] -(YO)n2- and n2 have the same meanings as in the general formula (1). A plurality of compounds in which n2 is different may be contained.

[0116] X in general formula (1) and general formula (10) is preferably general formula (11), general formula (12), or general formula (13); -(YO)n2- in general formula (1) and general formula (10) is preferably a structure arranged in general formula (14) or general formula (15), or more preferably a structure randomly arranged in general formula (14) and general formula (15).

[0117] [Chemistry 17]

[0118]

[0119] [Chemistry 18]

[0120]

[0121] In general formula (12), R 921 , R 922 , R 923 , R 924 , each independently represents a hydrogen atom or a methyl group. -B- is a linear, branched or cyclic divalent hydrocarbon group having 20 or less carbon atoms.

[0122] [Chemistry 19]

[0123]

[0124] In the general formula (13), -B- is a linear, branched or cyclic divalent hydrocarbon group having 20 or less carbon atoms.

[0125] [Chemistry 20]

[0126]

[0127] [Chemistry 21]

[0128]

[0129] The method for producing the modified polyphenylene ether having the structure represented by general formula (10) is not particularly limited. For example, the modified polyphenylene ether can be produced by etherifying the terminal phenolic hydroxyl group of a difunctional phenylene ether oligomer obtained by oxidative coupling of a difunctional phenol compound and a monofunctional phenol compound with a vinylbenzyl group.

[0130] As such modified polyphenylene ether, commercially available products may be used, and for example, OPE-2St1200 and OPE-2st2200 manufactured by Mitsubishi Gas Chemical Co., Ltd. may be preferably used.

[0131] The content of the polyphenylene ether compound (B) of the resin combination of the present embodiment, relative to the resin solids component of 100 mass parts of resin combinations, is preferably more than 1 mass part, more preferably more than 5 mass parts, further more preferably more than 8 mass parts.In addition, the upper limit value of aforementioned content, is preferably less than 40 mass parts, more preferably less than 30 mass parts, also can be less than 25 mass parts.By making the content of polyphenylene ether compound (B) in such a scope, there is the tendency of effectively reaching low dielectric constant, low dielectric loss tangent and good formability.

[0132] The resin composition may contain only one polyphenylene ether compound (B) or two or more thereof. When containing two or more thereof, the total amount is preferably within the above range.

[0133] [Block copolymer having a styrene skeleton (C)]

[0134] The "block copolymer (C) having a styrene skeleton" of the present embodiment refers to an elastomer of a block copolymer having a polystyrene block structure, and does not contain a random copolymer. In addition, a compound consisting only of an aromatic vinyl compound is not included in the "block copolymer (C) having a styrene skeleton". The resin composition of the present embodiment, by containing a block copolymer (C) having a styrene skeleton, can obtain excellent low dielectric constant, low dielectric loss tangent and flexibility.

[0135] The block copolymer (C) with a styrene skeleton used in the resin composition of the present embodiment preferably includes at least one selected from the group consisting of styrene-butadiene block copolymers, styrene-isoprene block copolymers, styrene-hydrogenated butadiene block copolymers, styrene-hydrogenated isoprene block copolymers and styrene-hydrogenated (isoprene / butadiene) block copolymers. Such block copolymers can be used alone or in combination of two or more. In particular, styrene-isoprene block copolymers, styrene-hydrogenated butadiene block copolymers, styrene-hydrogenated isoprene block copolymers, and styrene-hydrogenated (butadiene / isoprene) block copolymers are preferred because they impart a more excellent low dielectric loss tangent.

[0136] The polystyrene block structure of the present embodiment may be a styrene having a substituent, and specifically, a styrene derivative such as α-methylstyrene, 3-methylstyrene, 4-propylstyrene, or 4-cyclohexylstyrene may be used.

[0137] The styrene content (hereinafter referred to as "styrene rate") in the block copolymer (C) having a styrene skeleton is not particularly limited, but is preferably 10% by mass or more, and more preferably 20% by mass or more. The upper limit of the styrene content is not particularly limited as long as it is less than 100% by mass, for example, it is preferably less than 99% by mass, and more preferably less than 70% by mass. By making the styrene content such a range, there is a tendency to further improve solvent solubility and compatibility with other compounds. Here, the styrene content is a value shown as (a) / (b)×100 (unit: %) when the mass of the styrene unit contained in the block copolymer (C) having a styrene skeleton is (a) g and the mass of the block copolymer (C) having a styrene skeleton as a whole is (b) g.

[0138] The content of the block copolymer (C) with styrene skeleton in the resin composition of the present embodiment, relative to 100 mass parts of the resin solid content component of the resin composition, is preferably more than 1 mass part, more preferably more than 5 mass parts, and can also be more than 8 mass parts. The upper limit value of the aforementioned content is preferably less than 30 mass parts, more preferably less than 25 mass parts, and further more preferably less than 22 mass parts. By making its content such a scope, there is a tendency that low dielectric constant, low dielectric loss tangent and formability are more excellent. Resin composition, can contain only a kind of block copolymer (C) with styrene skeleton, can also contain two or more. In the case of containing more than two, preferably the total amount is within the above range.

[0139] The block copolymer (C) having a styrene skeleton in the present embodiment may also be a commercially available product. For example, styrene-butadiene-styrene block copolymers include TR2630 (manufactured by JSR (Strain)) and TR2003 (manufactured by JSR (Strain)). In addition, styrene-isoprene-styrene block copolymers include SIS5250 (manufactured by JSR (Strain)). Styrene-hydrogenated isoprene-styrene block copolymers include SEPTON2104 (manufactured by Kuraray (Strain)).

[0140] [Maleimide compound (D)]

[0141] The resin composition of the present embodiment preferably further contains a maleimide compound (D) other than the maleimide compound (A). The maleimide compound (D), for example, preferably contains at least one selected from the group consisting of the following general formulas (2), (3), (4) and (5). Therefore, low thermal expansion and heat resistance can be improved. In addition, the [maleimide compound (D)] used in the present embodiment is different from the [maleimide compound (A)] mentioned above.

[0142] [Chemistry 22]

[0143]

[0144] In general formula (2), R 41 , R 42 Each independently represents a hydrogen atom or a methyl group, preferably a hydrogen atom. In addition, in general formula (2), n4 represents an integer greater than 1, and the upper limit of n4 is generally 10. From the viewpoint of solubility in organic solvents, the upper limit of n4 is preferably 7, and more preferably 5. The compound represented by general formula (2) may also contain two or more compounds in which n4 is different.

[0145] [Chemistry 23]

[0146]

[0147] In general formula (3), R 501 , R 502 , R 503 , R 504 , R 505 , R 506 , R 507 , R 508 , R 509 , R 510 , R 511 , R 512 , each independently represents a hydrogen atom, an alkyl group having 1 to 8 carbon atoms (e.g., methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl), or a phenyl group. Among these, from the viewpoint of improving flame retardancy and metal foil (copper foil) peel strength, a group selected from the group consisting of a hydrogen atom, a methyl group, and a phenyl group is preferred, a hydrogen atom and a methyl group are more preferred, and a hydrogen atom is further preferred.

[0148] In general formula (3), 1≦n5≦10 is an integer. From the viewpoint of further improving solvent solubility, n5 is preferably 4 or less, more preferably 3 or less, and even more preferably 2 or less. The compound represented by general formula (3) may contain two or more compounds having different n5.

[0149] [Chemistry 24]

[0150]

[0151] In the above general formula (4), R 61 , R 62 , R 63 , R 64 Each independently represents a hydrogen atom, a methyl group or an ethyl group, and R 71 , R 72 Each independently represents a hydrogen atom or a methyl group. From the viewpoint of further improving low dielectric constant and low dielectric loss tangent properties, R 61 , R 62 , R 63 , R 64 A methyl group or an ethyl group is preferred. Examples of such compounds include 3,3'-diethyl-5,5'-dimethyl-4,4'-diphenylmethane bismaleimide.

[0152] [Chemistry 25]

[0153]

[0154] In general formula (5), R 81 , R 82 Each independently represents a hydrogen atom, a methyl group or an ethyl group. From the viewpoint of further improving low dielectric constant and low dielectric loss tangent properties, R81 , R 82 A methyl group is preferred. Examples of such compounds include 2,2-bis(4-(4-maleimidophenoxy)-phenyl)propane.

[0155] The maleimide compound (D) used in the present embodiment can use commercially available products. For example, the maleimide compound represented by general formula (2) can appropriately use "BMI-2300" manufactured by Yamato Chemical Industries, Ltd., the maleimide compound represented by general formula (3) can appropriately use "MIR-3000" manufactured by Nippon Kayaku Co., Ltd., the maleimide compound represented by general formula (4) can appropriately use "BMI-70" manufactured by K·I Chemical Co., Ltd., and the maleimide compound represented by general formula (5) can appropriately use "BMI-80" manufactured by K·I Chemical Co., Ltd.

[0156] The content of the maleimide compound (D) in the resin combination of the present embodiment can be appropriately set in response to desired characteristics, and is not particularly limited. The content of maleimide compound (D), in the case of containing and in the case where the resin solid content component in the resin combination is set to 100 mass parts, is preferably more than 1 mass part, more preferably more than 5 mass parts. The upper limit value is preferably less than 90 mass parts, more preferably less than 60 mass parts, further more preferably less than 40 mass parts, and can also be less than 30 mass parts. By making its content such a scope, there is a tendency to more effectively play high heat resistance, low water absorption.

[0157] The maleimide compound (D) may be used alone or in combination of two or more. When two or more are used, the total amount is preferably within the above range.

[0158] [Flame retardant (E)]

[0159] The resin composition of the present embodiment preferably contains a flame retardant (E) in order to improve the flame resistance. The flame retardant (E) used in the present embodiment can be a known flame retardant, for example, a halogen flame retardant such as brominated epoxy resin, brominated polycarbonate, brominated polystyrene, brominated styrene, brominated phthalimide, tetrabromobisphenol A, pentabromobenzyl (meth) acrylate, pentabromotoluene, tribromophenol, hexabromobenzene, decabromodiphenyl ether, bis-1,2-pentabromophenylethane, chlorinated polystyrene, chlorinated paraffin, etc., red phosphorus, tricresyl phosphate, triphenyl phosphate, methyl phosphate, etc. can be used. Phosphorus flame retardants such as phenyl diphenyl ester, tricresyl phosphate, trialkyl phosphate, dialkyl phosphate, tris(chloroethyl) phosphate, phosphazene, 1,3-phenylenedibis(2,6-xylyl phosphate), 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phenanthrene-10-oxide, inorganic flame retardants such as aluminum hydroxide, magnesium hydroxide, some boehmite, boehmite, zinc borate, antimony trioxide, and silicon flame retardants such as silicone rubber and silicone resin. Such flame retardants can be used alone or in combination of two or more. Among them, phosphorus flame retardants are preferred, especially 1,3-phenylenedibis(2,6-xylyl phosphate) because it is difficult to damage the low dielectric properties. The phosphorus content in the resin composition is preferably 0.1% to 5% by mass.

[0160] The content of the flame retardant (E), in the case of containing, is preferably more than 1 mass part, more preferably more than 5 mass parts relative to the resin solid content component in 100 mass parts of the resin composition. In addition, the upper limit of the above content is preferably less than 30 mass parts, more preferably less than 20 mass parts, and also less than 15 mass parts. Flame retardant (E) can be used only one, or more than two. In the case of using more than two, the total amount is preferably within the above range.

[0161] [Cyanate ester compound (F)]

[0162] The cyanate compound (F) of the present embodiment is not particularly limited as long as it is a resin having an aromatic portion substituted with at least one cyanooxy group (cyanate group) in the molecule.

[0163] Examples of the cyanate compound (F) of the present embodiment include compounds represented by general formula (23).

[0164] [Chemistry 26]

[0165]

[0166] In the general formula (23), Ar1 and Ar2 each independently represent a phenylene group which may have a substituent, a naphthylene group which may have a substituent, or a biphenylene group which may have a substituent. 101 , R 102Each is independently selected from a hydrogen atom, an alkyl group having 1 to 6 carbon atoms which may have a substituent, an aryl group having 6 to 12 carbon atoms which may have a substituent, an alkoxy group having 1 to 4 carbon atoms which may have a substituent, an aralkyl group having a substituent bonded to an alkyl group having 1 to 6 carbon atoms and an aryl group having 6 to 12 carbon atoms, or an alkylaryl group having a substituent bonded to an alkyl group having 1 to 6 carbon atoms and an aryl group having 6 to 12 carbon atoms. 81 represents the number of cyano groups bonded to Ar1, and is an integer of 1 to 3. 82 represents the number of cyano groups bonded to Ar2, and is an integer of 1 to 3. 83 is R bonded to Ar1 101 When Ar1 is phenylene, it is 4-n 81 , when Ar1 is naphthylene, it is 6-n 81 , when Ar1 is biphenylene, it is 8-n 81 .n 84 is R bonded to Ar2 102 When Ar2 is phenylene, it is 4-n 82 , when Ar2 is naphthylene, it is 6-n 82 , when Ar2 is biphenylene, it is 8-n 82 .n 85 represents the average number of repetitions, which is an integer from 0 to 50. The cyanate compound (F) may also be 85 It is a mixture of different compounds. Z is independently selected from a single bond, a divalent organic group having 1 to 50 carbon atoms (hydrogen atoms may be substituted with heteroatoms), a divalent organic group having 1 to 10 nitrogen atoms (-N-R-N-, etc.), a carbonyl group (-CO-), a carboxyl group (-C(=O)O-), a carbonyldioxy group (-OC(=O)O-), a sulfonyl group (-SO2-), and a divalent sulfur atom or a divalent oxygen atom.)

[0167] R of general formula (23) 101 , R 102 The alkyl group in the general formula (23) may have a linear structure, a branched structure, or a cyclic structure (cycloalkyl group, etc.). 101 , R 102 The hydrogen atom in the aryl group may be substituted by a halogen atom such as a fluorine atom or a chlorine atom, an alkoxy group such as a methoxy group or a phenoxy group, or a cyano group.

[0168] Specific examples of the alkyl group include methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, 1-ethylpropyl, 2,2-dimethylpropyl, cyclopentyl, hexyl, cyclohexyl, and trifluoromethyl.

[0169] Specific examples of the aryl group include phenyl, xylyl, mesityl, naphthyl, phenoxyphenyl, ethylphenyl, o-, m- or p-fluorophenyl, dichlorophenyl, dicyanophenyl, trifluorophenyl, methoxyphenyl, o-, m- or p-tolyl.

[0170] Specific examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, an n-butoxy group, an isobutoxy group, and a tert-butoxy group.

[0171] Specific examples of the divalent organic group in Z of the general formula (23) include methylene, ethylene, trimethylene, cyclopentylene, cyclohexylene, trimethylcyclohexylene, biphenylene methylene, dimethyl methylene-phenylene-dimethyl methylene, fluorenyl, phthalyl, etc. The hydrogen atom in the aforementioned divalent organic group may be substituted by a halogen atom such as a fluorine atom or a chlorine atom, an alkoxy group such as a methoxy group or a phenoxy group, a cyano group, etc. The divalent organic group having 1 to 10 nitrogen atoms in Z of the general formula (23) includes an imide group, a polyimide, etc.

[0172] In addition, Z in the general formula (23) may have a structure represented by the following general formula (24) or the following general formula (25).

[0173] [Chemistry 27]

[0174]

[0175] In the general formula (24), Ar3 is any one selected from phenylene, naphthylene, and biphenylene. 103 , R 104 , R 107 , R 108 Each is independently selected from any one of a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a trifluoromethyl group, and an aryl group substituted with at least one of a phenolic hydroxyl group. 105 , R 106 Each is independently selected from any one of a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, and a hydroxyl group. 86 is an integer of 0 to 5, except that the cyanate compound (F) may also be an integer having n 86 A mixture of compounds of different groups.

[0176] [Chemistry 28]

[0177]

[0178] In the general formula (25), Ar4 is any one selected from phenylene, naphthylene or biphenylene. 109 , R 110Each independently selected from any one of an aryl group substituted with at least one of a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a benzyl group, an alkoxy group having 1 to 4 carbon atoms, a hydroxyl group, a trifluoromethyl group, and a cyano group. 87 is an integer of 0 to 5, except that the cyanate compound (F) may also be an integer having n 87 A mixture of compounds with different groups.

[0179] Furthermore, Z in the general formula (23) includes divalent groups represented by the following formulas.

[0180] [Chemistry 29]

[0181]

[0182] Where n 88 is an integer representing 4 to 7. 111 , R 112 Each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.

[0183] Specific examples of Ar3 in the general formula (24) and Ar4 in the general formula (25) include 1,4-phenylene, 1,3-phenylene, 4,4'-biphenylene, 2,4'-biphenylene, 2,2'-biphenylene, 2,3'-biphenylene, 3,3'-biphenylene, 3,4'-biphenylene, 2,6-naphthylene, 1,5-naphthylene, 1,6-naphthylene, 1,8-naphthylene, 1,3-naphthylene, 1,4-naphthylene, etc. R in the general formula (24) 103 ~R 108 And R of general formula (25) 109 , R 110 The alkyl and aryl groups are the same as those described in the general formula (23).

[0184] Cyanate compounds represented by general formula (23) include, for example, novolac-type cyanate compounds, naphthol aralkyl-type cyanate compounds, biphenyl aralkyl-type cyanate compounds, naphthol ether-type cyanate compounds, xylene resin-type cyanate compounds, adamantane skeleton-type cyanate compounds, bisphenol A-type cyanate compounds, diallyl bisphenol A-type cyanate compounds, naphthol aralkyl-type cyanate compounds, and the like.

[0185] Specific examples of the cyanate compound represented by the general formula (23) include cyanobenzene, 1-cyano-2-, 1-cyano-3-, or 1-cyano-4-methylbenzene, 1-cyano-2-, 1-cyano-3-, 1-cyano-4-methoxybenzene, 1-cyano-2,3-, 1-cyano-2,4-, 1-cyano-2,4-, 1-cyano-2,5-, 1-cyano-2,6-, 1-cyano-3,4- or 1-cyano-3,5-dimethylbenzene, cyanoethylbenzene, cyanobutylbenzene, cyanooctylbenzene, cyanononylbenzene, 2-(4-cyanophenyl)-2-phenylpropane (cyanate of 4-α-cumylphenol), 1-cyano-4-cyclohexylbenzene, 1-cyano- 1-cyano-4-vinylbenzene, 1-cyano-2- or 1-cyano-3-chlorobenzene, 1-cyano-2,6-dichlorobenzene, 1-cyano-2-methyl-3-chlorobenzene, cyanonitrobenzene, 1-cyano-4-nitro-2-ethylbenzene, 1-cyano-2-methoxy-4-allylbenzene (cyanate of eugenol), methyl (4-cyanophenyl) sulfide, 1-cyano-3-trifluoromethylbenzene, 4-cyanobiphenyl, 1-cyano-2- or 1-cyano-4-acetophenone, 4-cyanobenzaldehyde, 4-cyanobenzoic acid methyl ester, 4-cyanobenzoic acid phenyl ester, 1-cyano-4-acetamidobenzene, 4-cyanobenzophenone, 1-cyano-2,6-di-tert-butylbenzene, 1,2-dicyano Oxybenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, 1,4-dicyano-2-tert-butylbenzene, 1,4-dicyano-2,4-dimethylbenzene, 1,4-dicyano-2,3,4-trimethylbenzene, 1,3-dicyano-2,4,6-trimethylbenzene, 1,3-dicyano-5-toluene, 1-cyano or 2-cyano naphthalene, 1-cyano-4-methoxynaphthalene, 2-cyano-6-methylnaphthalene, 2-cyano-7-methoxynaphthalene, 2,2'-dicyano-1,1'-binaphthyl, 1,3-, 1,4-, 1,5-, 1,6-, 1,7-, 2,3-, 2,6- or 2,7-dicyanonaphthalene, 2,2'- or 4,4'-dicyanobiphenyl, 4,4' -bis(4-cyanophenyl)propane, 2,2-bis(4-cyanophenyl)propane, 2,2-bis(3-allyl-4-cyanophenyl)propane, 2,2-bis(4-cyanophenyl)propane, 2,2-bis(4-cyanophenyl)propane, 2,2-bis(2-cyano-5-biphenyl)propane, 2,2-bis(4-cyanophenyl)hexafluoropropane, 2,2-bis(4-cyanophenyl)propane, 1,1-bis(4-cyanophenyl)butane, 1,1-bis(4-cyanophenyl)isobutane, 1,1-bis(4-cyanophenyl)butane, 1,1-bis(4-cyanophenyl)isobutane, 1,1-bis(4-cyanophenyl)hexafluoropropane, 2,2-bis(4-cyanophenyl)propane, 1,1-bis(4-cyanophenyl)isobut ...1-bis(4-cyanophenyl)pentane, 1,1-bis(4-cyanophenyl)-3-methylbutane, 1,1-bis(4-cyanophenyl)-2-methylbutane, 1,1-bis(4-cyanophenyl)-2,2-dimethylpropane, 2,2-bis(4-cyanophenyl)butane, 2,2-bis(4-cyanophenyl)pentane, 2,2-bis(4-cyanophenyl)hexane, 2,2-bis(4-cyanophenyl)-3-methylbutane, 2,2-bis(4-cyanophenyl)-4-methylpentane, 2,2-bis(4-cyanophenyl)-3,3-dimethylbutane, 3,3-bis(4-cyanophenyl)hexane, 3,3-bis(4-cyanophenyl)heptane, 3,3-bis(4-cyanophenyl) 3,3-bis(4-cyanophenyl)-2-methylpentane, 3,3-bis(4-cyanophenyl)-2-methylhexane, 3,3-bis(4-cyanophenyl)-2,2-dimethylpentane, 4,4-bis(4-cyanophenyl)-3-methylheptane, 3,3-bis(4-cyanophenyl)-2-methylheptane, 3,3-bis(4-cyanophenyl)-2,2-dimethylhexane, 3,3-bis(4-cyanophenyl)-2,4-dimethylhexane, 3,3-bis(4-cyanophenyl)-2,2,4-trimethylpentane, 2,2-bis(4-cyanophenyl)-1,1,1,3,3,3-hexafluoropropane, bis(4-cyanophenyl)phenylmethane, 1,1-bis(4-cyanophenyl)-1,1,1,3,3,3-hexafluoropropane (4-cyanophenyl)-1-phenylethane, bis(4-cyanophenyl)biphenylmethane, 1,1-bis(4-cyanophenyl)cyclopentane, 1,1-bis(4-cyanophenyl)cyclohexane, 2,2-(4-cyanophenyl-3-isopropylphenyl)propane, 1,1-bis(3-cyclohexyl-4-cyanophenyl)cyclohexane, bis(4-cyanophenyl)diphenylmethane, bis(4-cyanophenyl)-2,2-dichloroethylene, 1,3-bis[2-(4-cyanophenyl)-2-propyl]benzene, 1,4-bis[2-(4-cyanophenyl)-2-propyl]benzene, 1,1-bis(4-cyanophenyl)-3,3,5-trimethylcyclohexane, 4-[bis(4-cyanophenyl)methyl]biphenyl, 4 ,4-dicyanobenzophenone, 1,3-bis(4-cyanophenyl)-2-propene-1-one, bis(4-cyanophenyl) ether, bis(4-cyanophenyl) sulfide, bis(4-cyanophenyl) sulfone, 4-cyanophenyl 4-cyanobenzoate (4-cyanophenyl-4-cyanobenzoate), bis-(4-cyanophenyl) carbonate, 1,3-bis(4-cyanophenyl) adamantane, 1,3-bis(4-cyanophenyl)-5,7-dimethyladamantane, 3,3-bis(4-cyanophenyl)isobenzofuran-1(3H)-one (cyanate of phenolphthalein), 3,3-bis(4-cyano-3-methylphenyl)isobenzofuran-1(3H)-one (o-cresolphthalein cyanate), 9,9-bis(4-cyanophenyl)fluorene, 9,9-bis(4-cyano-3-methylphenyl)fluorene, 9,9-bis(2-cyano-5-biphenyl)fluorene, tris(4-cyanophenyl)methane, 1,1,1-tris(4-cyanophenyl)ethane, 1,1,3-tris(4-cyanophenyl)propane, α,α,α'-tris(4-cyanophenyl)-1-ethyl-4-isopropylbenzene, 1,1,2,2-tetrakis(4-cyanophenyl)ethane, tetrakis(4-cyanophenyl)propane phenyl)methane, 2,4,6-tris(N-methyl-4-cyanoanilino)-1,3,5-triazine, 2,4-bis(N-methyl-4-cyanoanilino)-6-(N-methylanilino)-1,3,5-triazine, bis(N-4-cyano-2-methylphenyl)-4,4'-oxydiphthalimide, bis(N-3-cyano-4-methylphenyl)-4,4'-oxydiphthalimide, bis(N-4-cyanophenyl)-4,4'- Oxydiphthalimide, bis(N-4-cyano-2-methylphenyl)-4,4'-(hexafluoroisopropylpyridine)diphthalimide, tris(3,5-dimethyl-4-cyanobenzyl)isocyanurate, 2-phenyl-3,3-bis(4-cyanophenyl)benzylcarboxylic acid lactam, 2-(4-methylphenyl)-3,3-bis(4-cyanophenyl)benzylcarboxylic acid lactam, 2-phenyl-3,3-bis(4-cyano-3-methylphenyl)benzylcarboxylic acid lactam, 1-methyl 2-phenyl-3,3-bis(4-cyanophenyl)indolin-2-one, 2-phenyl-3,3-bis(4-cyanophenyl)indolin-2-one, novolac resin or cresol novolac resin (reacted in an acidic solution with phenol, alkyl-substituted phenol or halogen-substituted phenol, and a formaldehyde compound such as formalin or polyoxymethylene by a conventional method), trisphenol novolac resin (reacted with hydroxybenzaldehyde and phenol in the presence of an acidic catalyst), fluorene novolac resin (reacted with a fluorene ketone compound and 9,9-bis(hydroxyaryl)fluorenone reacted in the presence of an acidic catalyst), phenol aralkyl resin, cresol aralkyl resin, naphthol aralkyl resin or biphenyl aralkyl resin (by a conventional method, a dihalomethyl compound represented by Ar5-(CH2Z')2 is reacted with a phenol compound in the presence of an acidic catalyst or in the absence of a catalyst; a bis(alkoxymethyl) compound represented by Ar5-(CH2OR)2 or a bis(hydroxymethyl) compound represented by Ar5-(CH2OH)2 is reacted with a phenol compound in the presence of an acidic catalyst; or an aromatic aldehyde compound, an aralkyl compound, a phenolic compound The phenol resins may be cyanate-esterified by the same method as above, such as phenolic resins (those obtained by reacting a phenolic resin with a phenol compound in the presence of an acidic catalyst by a known method), phenol-modified xylene formaldehyde resin (those obtained by reacting a xylene formaldehyde resin with a phenol compound in the presence of an acidic catalyst by a known method), modified naphthalene formaldehyde resin (those obtained by reacting a naphthalene formaldehyde resin with a hydroxy-substituted aromatic compound in the presence of an acidic catalyst by a known method), phenol-modified dicyclopentadiene resin, and phenolic resins having a polynaphthalene ether structure (those obtained by dehydrating and condensing a polyvalent hydroxynaphthalene compound having two or more phenolic hydroxyl groups in one molecule in the presence of an alkaline catalyst by a known method), etc., but are not particularly limited. Such cyanate compounds may be used alone or in combination of two or more.

[0186] Among them, preferred are novolac type cyanate ester compounds, naphthol aralkyl type cyanate ester compounds, naphthol ether type cyanate ester compounds, bisphenol A type cyanate ester compounds, bisphenol M type cyanate ester compounds, and bisallyl bisphenol type cyanate ester compounds, and particularly preferred are naphthol aralkyl type cyanate ester compounds.

[0187] The cured product of the resin composition using such a cyanate ester compound has excellent properties such as heat resistance and copper foil adhesion.

[0188] The content of the cyanate compound (F) of the resin composition of the present embodiment can be appropriately set in response to desired characteristics, and is not particularly limited. Specifically, the content of the cyanate compound (F), the resin solid content component in the resin composition is the situation of 100 mass parts, preferably more than 0.1 mass parts, more preferably more than 0.5 mass parts, more preferably more than 1 mass parts, also can be more than 3 mass parts, more than 5 mass parts. In addition, the upper limit value of the aforementioned content, preferably less than 90 mass parts, more preferably less than 80 mass parts, further more preferably less than 70 mass parts, and further more preferably less than 60 mass parts, also can be less than 50 mass parts, less than 40 mass parts. By making its content such a scope, more excellent low dielectric constant, low dielectric loss tangent can be given.

[0189] The cyanate compound (F) may be used alone or in combination of two or more. When two or more cyanate compounds are used, the total amount is preferably within the above range.

[0190] [Other ingredients]

[0191] Furthermore, the resin composition of the present embodiment may contain, within the range of obtaining the desired properties, a polyphenylene ether compound other than the aforementioned polyphenylene ether compound (B), an epoxy compound, a phenol compound, an oxetane resin, a benzoxazine compound, a thermoplastic elastomer not described in the aforementioned block copolymer (C) having a styrene skeleton (hereinafter referred to as "other thermoplastic elastomer"), a filler (G), a curing accelerator, an organic solvent, etc. By using these in combination, the desired properties such as low dielectric constant, low dielectric loss tangent, flame retardancy and low thermal expansion can be improved.

[0192] The total amount of the polyphenylene ether compound other than the polyphenylene ether compound (B) and the other thermoplastic elastomers in the resin composition of the present embodiment is preferably 3% by mass or less of the resin solid content, and more preferably 1% by mass or less. By such a configuration, the effect of the present invention can be more effectively exerted.

[0193] [Epoxides]

[0194] The epoxy compound is not particularly limited as long as it is a compound or resin having 1 or more (preferably 2 to 12, more preferably 2 to 6, further preferably 2 to 4, and further preferably 2 or 3) epoxy groups in one molecule, and compounds commonly used in the field of printed circuit boards can be widely used.

[0195] Examples of the epoxy compound include bisphenol A epoxy resin, bisphenol E epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, bisphenol A novolac epoxy resin, glycidyl ester epoxy resin, arane novolac epoxy resin, biphenyl arane epoxy resin, naphthol ether epoxy resin, cresol novolac resin, polyfunctional phenol epoxy resin, naphthalene epoxy resin, anthracene epoxy resin, naphthalene skeleton modified novolac epoxy resin, phenol arane epoxy resin, naphthol arane epoxy resin, dicyclopentadiene epoxy resin, biphenyl epoxy resin, alicyclic epoxy resin, polyol epoxy resin, phosphorus-containing epoxy resin, glycidylamine, glycidyl ester, compounds obtained by epoxidizing double bonds of butadiene or the like, compounds obtained by reacting hydroxyl-containing silicone resins with epichlorohydrin, and the like. These epoxy resins can be used alone or in combination of two or more. Among these, biphenyl aralkyl epoxy resins, naphthol ether epoxy resins, multifunctional phenol epoxy resins, and naphthalene epoxy resins are preferred from the viewpoint of further improving flame retardancy and heat resistance.

[0196] [Phenol compounds]

[0197] The phenol compound is not particularly limited as long as it is a compound or resin having 1 or more (preferably 2 to 12, more preferably 2 to 6, further preferably 2 to 4, further preferably 2 or 3, further preferably 2) phenolic hydroxyl groups in one molecule, and examples thereof include bisphenol A type phenol resin, bisphenol E type phenol resin, bisphenol F type phenol resin, bisphenol S type phenol resin, novolac type resin, bisphenol A novolac type phenol resin, glycidyl ester type phenol resin, aralkyl novolac type phenol resin, biphenylaralkyl type phenol resin, cresol novolac type resin, multifunctional phenol resin, naphthol resin, naphthol novolac resin, multifunctional naphthol resin, anthracene type phenol resin, naphthalene skeleton modified novolac type phenol resin, phenolaralkyl type phenol resin, naphtholaralkyl type phenol resin, dicyclopentadiene type phenol resin, biphenyl type phenol resin, alicyclic type phenol resin, polyol type phenol resin, phosphorus-containing phenol resin, etc. Such phenol resins may be used alone or in combination of two or more. Among these, at least one selected from the group consisting of biphenylarane type phenol resins, naphtholarane type phenol resins, phosphorus-containing phenol resins, and hydroxyl-containing silicone resins is preferred from the viewpoint of further improving flame retardancy.

[0198] [Oxetane resin]

[0199] The oxetane resin is not particularly limited, and examples thereof include oxetane, alkyloxetane (e.g., 2-methyloxetane, 2,2-dimethyloxetane, 3-methyloxetane, 3,3-dimethyloxetane, etc.), 3-methyl-3-methoxymethyloxetane, 3,3-bis(trifluoromethyl)perfluorooxetane, 2-chloromethyloxetane, 3,3-bis(chloromethyl)oxetane, biphenyl-type oxetane, OXT-101 (a product of Toagosei Co., Ltd.), and OXT-121 (a product of Toagosei Co., Ltd.). These oxetane resins may be used alone or in combination of two or more.

[0200] [Benzoxazine compounds]

[0201] The benzoxazine compound is not particularly limited as long as it is a compound having two or more dihydrobenzoxazine rings in one molecule, and examples thereof include bisphenol A type benzoxazine BA-BXZ (a product of Konishi Chemical Co., Ltd.), bisphenol F type benzoxazine BF-BXZ (a product of Konishi Chemical Co., Ltd.), and bisphenol S type benzoxazine BS-BXZ (a product of Konishi Chemical Co., Ltd.). These benzoxazine compounds may be used alone or in combination of two or more.

[0202] [Other thermoplastic elastomers]

[0203] "Other thermoplastic elastomers" are distinguished from "block copolymers (C) having a styrene skeleton". "Block copolymers (C) having a styrene skeleton" refers to elastomers having a polystyrene block structure and being block copolymers; "other thermoplastic elastomers" refers to elastomers other than these. That is, random copolymers and block copolymers without a styrene skeleton should be included. Other thermoplastic elastomers include, for example, at least one selected from the group consisting of polyisoprene, polybutadiene, styrene-butadiene random copolymers, butyl rubber, ethylene-propylene rubber, fluororubber, silicone rubber, hydrogenated compounds thereof, and alkyl compounds thereof. Among these, from the viewpoint of better compatibility with the polyphenylene ether compound (B), at least one selected from the group consisting of polyisoprene, polybutadiene, styrene-butadiene random copolymers, butyl rubber, and ethylene-propylene rubber is more preferred.

[0204] [Filling material (G)]

[0205] Filler (G) may be a known material as appropriate, and its type is not particularly limited, and those commonly used in the general knowledge of the field may be appropriately used. Specifically, there may be listed: silicas such as natural silica, fused silica, synthetic silica, amorphous silica, fumed silica (Aerosil), hollow silica, etc.; white carbon, titanium dioxide, zinc oxide, magnesium oxide, zirconium oxide, boron nitride, agglomerated boron nitride, silicon nitride, aluminum nitride, barium sulfate, aluminum hydroxide, aluminum hydroxide heat-treated product (aluminum hydroxide heat-treated to reduce a portion of the crystal water), boehmite, magnesium hydroxide, etc.; molybdenum compounds such as molybdenum oxide or zinc molybdate; zinc borate, zinc stannate, aluminum oxide, In addition to inorganic fillers such as clay, kaolin, talc, calcined clay, calcined kaolin, calcined talc, mica, E-glass, A-glass, NE-glass, C-glass, L-glass, D-glass, S-glass, M-glass G20, short glass fibers (including glass fine powders such as E glass, T glass, D glass, S glass, Q glass, etc.), hollow glass, spherical glass, etc., styrene type, butadiene type, acrylic type, etc. rubber powder; core-shell type rubber powder, silicone resin powder, silicone rubber powder, silicone composite powder, etc. organic fillers, etc. These fillers may be used alone or in combination of two or more.

[0206] Among these, one or more selected from the group consisting of silicon dioxide, aluminum hydroxide, boehmite, magnesium oxide and magnesium hydroxide are suitable. By using such fillers (G), the thermal expansion characteristics, dimensional stability, flame retardancy and other properties of the resin composition are improved.

[0207] The content of the filler (G) in the resin composition can be appropriately set in response to the desired characteristics, and is not particularly limited. The content of the filler (G), the situation containing the resin solid content component in the resin composition is set to 100 mass parts, preferably more than 50 mass parts. In addition, the upper limit of the content of the filler (G), the situation that the resin solid content component in the resin composition is set to 100 mass parts, is preferably less than 1600 mass parts, more preferably less than 500 mass parts, and particularly preferably less than 300 mass parts. Alternatively, the filler (G) can be 75 mass parts to 250 mass parts, or can be 100 mass parts to 200 mass parts. By making the content of the filler (G) this range, the formability of the resin composition becomes good.

[0208] The resin composition is a filler (G), and may contain only one type or two or more types. When containing two or more types, the total amount is preferably within the above range.

[0209] When the filler (G) is used here, it is preferred to use at least one selected from the group consisting of a silane coupling agent and a wetting dispersant. As the silane coupling agent, those generally used for the surface treatment of inorganic substances can be appropriately used, and the type thereof is not particularly limited. Specifically, there can be cited: aminosilane systems such as γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, etc.; epoxysilane systems such as γ-glycidoxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, etc.; vinylsilane systems such as γ-methacryloxypropyltrimethoxysilane, vinyl-tri(β-methoxyethoxy)silane, etc.; cationic silane systems such as N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane hydrochloride, etc.; phenylsilane systems, etc. The silane coupling agent can be used alone or in combination of two or more. In addition, the wetting dispersant can be appropriately used for coatings, and its type is not particularly limited. It is preferably a copolymer-based wetting dispersant, and specific examples thereof include Disperbyk-110, 111, 161, 180, 2009, 2152, BYK-W996, BYK-W9010, BYK-W903, BYK-W940, etc. manufactured by BYK Chemical Co., Ltd. of Japan. The wetting dispersant can be used alone or in combination of two or more.

[0210] The content of the silane coupling agent is not particularly limited, and may be about 1 to 5 parts by mass relative to 100 parts by mass of the resin solid content in the resin composition. The content of the dispersant (particularly the wetting dispersant) is not particularly limited, and may be, for example, about 0.5 to 5 parts by mass relative to 100 parts by mass of the resin solid content in the resin composition.

[0211] [Hardening accelerator]

[0212] The resin composition of the present embodiment may also contain a hardening accelerator for appropriately adjusting the hardening speed. The hardening accelerator may include maleimide compounds, cyanate compounds, epoxy compounds, etc. Commonly used hardening accelerators include organic metal salts (e.g., zinc octanoate, zinc naphthenate, cobalt naphthenate, copper naphthenate, iron acetylacetonate, nickel octanoate, manganese octanoate, etc.), phenol compounds (e.g., phenol, xylenol, cresol, resorcinol, catechol, octylphenol, nonylphenol, etc.), alcohols (e.g., 1-butanol, 2-ethylhexanol, etc.), imidazoles (e.g., 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-phenylimidazole -4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, etc.) and derivatives of such imidazole carboxylic acids or their anhydride adducts, amines (e.g., dicyandiamide, benzyldimethylamine, 4-methyl-N,N-dimethylbenzylamine, etc.), phosphorus compounds (e.g., phosphine compounds, phosphine oxide compounds, phosphonium salt compounds, diphosphine compounds, etc.), epoxy-imidazole adducts, peroxides (e.g., benzoyl peroxide, p-chlorobenzoyl peroxide, di-t-butyl peroxide, diisopropyl peroxycarbonate, di-2-ethylhexyl peroxycarbonate, etc.), azo compounds (e.g., azobisisobutyronitrile, etc.). The hardening accelerator may be used alone or in combination of two or more.

[0213] The content of the curing accelerator may generally be about 0.005 parts by mass to about 10 parts by mass based on 100 parts by mass of the resin solid content in the resin composition.

[0214] The resin composition of this embodiment may also contain various polymer compounds and various additives such as other thermosetting resins, thermoplastic resins, and oligomers thereof other than the above-mentioned components. Examples of additives include ultraviolet absorbers, antioxidants, photopolymerization initiators, fluorescent whitening agents, photosensitizers, dyes, pigments, tackifiers, flow regulators, lubricants, defoamers, dispersants, leveling agents, glossing agents, polymerization inhibitors, etc. These additives may be used alone or in combination of two or more.

[0215] [Organic solvents]

[0216] The resin composition of the present embodiment may also contain an organic solvent. In this case, the resin composition of the present embodiment is a form (solution or varnish) in which at least a part of the above-mentioned various resin components, preferably all of them, are dissolved or soluble in an organic solvent. The organic solvent is not particularly limited as long as it can dissolve or dissolve at least a part of the above-mentioned various resin components, preferably all of them, and is a polar organic solvent or a non-polar organic solvent; polar organic solvents, for example, can include: ketones (for example, acetone, methyl ethyl ketone, methyl isobutyl ketone, etc.), cellosolves (for example, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, etc.), esters (for example, ethyl lactate, methyl acetate, ethyl acetate, butyl acetate, isoamyl acetate, ethyl lactate, methyl methoxypropionate, methyl hydroxyisobutyrate, etc.), amides (for example, dimethoxyacetamide, dimethylformamide, etc.); non-polar organic solvents can include aromatic hydrocarbons (for example, toluene, xylene, etc.). Such organic solvents can be used alone or in combination of two or more.

[0217] [Preparation of resin composition]

[0218] The resin composition of the present embodiment can be prepared according to conventional methods. As long as the method for obtaining the resin composition is to uniformly contain: a maleimide compound (A) having an aromatic ring in the main skeleton and a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, a polyphenylene ether compound (B) having a number average molecular weight of 1000 or more and 7000 or less as shown in the general formula (1), a block copolymer (C) having a styrene skeleton, and any other components mentioned above, then the preparation method is not particularly limited. For example, the maleimide compound (A), the polyphenylene ether compound (B) shown in the general formula (1), and the block copolymer (C) having a styrene skeleton are sequentially mixed in a solvent and stirred sufficiently to easily prepare the resin composition of the present embodiment. In the resin composition of this embodiment, the sum of the masses of the maleimide compound (A), the polyphenylene ether compound (B) represented by the general formula (1), and the block copolymer (C) having a styrene skeleton preferably accounts for more than 40% by mass of the resin solid content contained in the resin composition, more preferably more than 45% by mass, and may also account for more than 50% by mass.

[0219] [use]

[0220] The resin composition of the present embodiment can be suitably used as a resin sheet, a prepreg, an insulating layer of a printed wiring board, a build-up board, and a semiconductor packaging material.

[0221] [Resin sheet]

[0222] The resin sheet of the present embodiment has a support and a layer formed by the resin composition of the present embodiment disposed on the surface of the support. The resin sheet can be used as a thin film for layer building or a dry film solder resist. The method for manufacturing the resin sheet is not particularly limited, and for example, a method of obtaining the resin sheet by applying (coating) a solution prepared by dissolving the resin composition of the present embodiment in a solvent to a support and drying the solution can be cited.

[0223] The support used here, for example, can be listed: polyethylene film, polypropylene film, polycarbonate film, polyethylene terephthalate film, ethylene tetrafluoroethylene copolymer film, and the release film of the release agent coated on the surface of the film, polyamide film and other organic film substrates, copper foil, aluminum foil and other conductor foils, glass plates, SUS plates, FRP and other plate-like persons, but not particularly limited. Copper foil, preferably the layer formed by the resin composition of the present embodiment is the ten-point average roughness Rz of the surface of the copper foil on the configuration side is 0.3 μm or more and 10 μm or less. By being 0.3 μm or more, the plating adhesion can be improved. In addition, if it is greater than 10 μm, in order to ensure insulation, the thickness of the layer formed by the resin composition of the present embodiment must be thickened. The more preferred range of the ten-point average roughness Rz of the surface of the copper foil is, for example, 0.6 μm or more and 2.5 μm or less. Furthermore, the ten-point average roughness Rz of the surface of the copper foil is preferably less than the thickness of the layer formed by the resin composition of the present embodiment. Thus, the insulation is improved. The ten-point average roughness Rz of the surface of the copper foil can be measured using a commercially available shape measuring microscope (laser microscope, for example, Keynes Co., Ltd., "VK-X1000" (trade name)).

[0224] The thickness of the copper foil is not particularly limited, but is preferably in the range of 1 μm to 18 μm in consideration of surface roughening. In order to appropriately obtain a thin printed wiring board and a semiconductor device mounting substrate, it is more preferably in the range of 2 μm to 15 μm.

[0225] Examples of the coating method include a method of coating a solution of the resin composition of the present embodiment dissolved in a solvent on a support using a gravure coater, a bar coater, a die coater, a doctor blade, a baker coater, or the like.

[0226] In addition, in the preparation of the resin sheet of the present embodiment, the drying conditions when removing the solvent are not particularly limited. From the perspective of easily removing the solvent in the resin composition and inhibiting the progress of curing during drying, it is preferably carried out at a temperature of 20°C to 200°C for 1 minute to 90 minutes. In addition, in the resin sheet of the present embodiment, the resin composition can also be used in an uncured state where only the solvent is dried, or it can be used in a semi-cured (B-staged) state as needed. Furthermore, the thickness of the resin layer of the resin sheet of the present embodiment can be adjusted by the concentration of the solution of the resin composition of the present embodiment and the coating thickness, and is not particularly limited. From the perspective of easily removing the solvent during drying, it is preferably 0.1μm to 500μm.

[0227] [Prepreg]

[0228] The prepreg of the present embodiment is formed by a substrate and a resin composition of the present embodiment. The prepreg of the present embodiment is obtained by, for example, impregnating or coating the resin composition of the present embodiment on a substrate and then drying it at 120°C to 220°C for about 2 minutes to 15 minutes to semi-harden it. In this case, the amount of the resin composition attached to the substrate, that is, the amount of the resin composition (including the filler (G)) relative to the total amount of the semi-hardened prepreg, is preferably in the range of 20% to 90% by mass.

[0229] The substrate is not particularly limited as long as it is a substrate used for various printed circuit board materials. The material of the substrate, for example, can be listed as: glass fiber (for example, E glass, D glass, L glass, S glass, T glass, Q glass, UN glass, NE glass, spherical glass), inorganic fiber other than glass (for example, quartz), or organic fiber (for example, polyimide, polyamide, polyester, liquid crystal polyester, polytetrafluoroethylene). The form of the substrate is not particularly limited, and can be listed as woven fabric, non-woven fabric, roving, chopped strand mat, surface mat, etc. Such substrates can be used alone or in combination of two or more. Among such substrates, from the viewpoint of dimensional stability, it is preferably a woven fabric treated with super fiber opening and filling; from the viewpoint of moisture absorption and heat resistance, it is preferably a glass fabric surface-treated with a silane coupling agent such as epoxy silane treatment and amino silane treatment.

[0230] The prepreg is obtained, for example, by impregnating or coating a substrate with a resin composition and then semi-curing (B-stage) it by drying at 120°C to 220°C for about 2 minutes to 15 minutes. In this case, the amount of the resin composition (including the cured product of the resin composition) attached to the substrate, that is, the amount of the resin composition (including the filler (G)) relative to the total amount of the semi-cured prepreg, is preferably in the range of 20% to 99% by mass. The thickness or mass of the substrate is not particularly limited, and generally, a thickness of about 0.01mm to 0.3mm is suitable. In particular, from the viewpoint of strength and water absorption, the substrate is preferably 200μm or less in thickness and 250g / m 2 The following weaving.

[0231] [Laminated board]

[0232] Laminated boards are obtained by heating and pressurizing a laminate containing one or more prepregs and hardening the prepregs. The forming method and forming conditions of the laminated board are not particularly limited, and general techniques and conditions can be used. For example, a multi-stage press, a multi-stage vacuum press, a continuous forming machine, an autoclave forming machine, etc. can be used during forming. During forming (laminated forming), the temperature is generally 100°C to 300°C and the pressure is a surface pressure of 2kgf / cm 2 ~100kgf / cm 2 , heating time is in the range of 0.05 hours to 5 hours. Furthermore, if necessary, post-hardening can be performed at a temperature of 150°C to 300°C. In particular, when a multi-stage press is used, from the perspective of fully promoting the hardening of the prepreg, the preferred temperature is 200°C to 250°C and the pressure is 10 kgf / cm 2 ~40kgf / cm 2 , heating time 80 minutes to 130 minutes, preferably temperature 215 ℃ to 235 ℃, pressure 25kgf / cm 2 ~35kgf / cm 2 , heating time 90 minutes to 120 minutes.

[0233] [Printed Circuit Board]

[0234] The printed circuit board of this embodiment comprises an insulating layer and a conductor layer disposed on the surface of the insulating layer, wherein the insulating layer comprises a layer formed by the resin composition of this embodiment. The resin sheet of this embodiment can be used for a printed circuit board. Here, the printed circuit board is a metal foil-clad laminated board in which the insulating resin layer, which can be referred to as a core substrate, is completely hardened, and is obtained by using the resin sheet of this embodiment as a build-up material, for example, a copper foil with an insulating resin layer (resin composition layer).

[0235] On the surface of the metal foil-clad laminate, a conductor circuit is formed by stripping the metal foil of the commonly used metal foil-clad laminate and / or plating the conductor layer obtained by the metal foil. In addition, the base material of the metal foil-clad laminate is not particularly limited, and mainly includes a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate.

[0236] In the present embodiment, the build-up layer means laminating the resin sheet of the present embodiment, for example, an insulating resin layer of a copper foil with an insulating resin layer, on the metal foil and / or conductor layer on the surface of the metal foil-clad laminate.

[0237] In general, when an insulating resin layer (resin composition layer) is laminated on a metal foil-clad laminate using an adhesive film or the like as a build-up material, the resulting printed circuit board has an insulating resin layer on one or both sides. Although a conductor layer is formed on the insulating resin layer, since the surface roughness of the insulating resin layer after curing is low, generally, roughening treatment including desmear treatment is performed to form unevenness, and then the conductor layer is formed by electroless plating and / or electrode plating.

[0238] The resin sheet of the present embodiment as a build-up material, for example, when a copper foil with an insulating resin layer is laminated on a metal foil-clad laminate, the resulting printed circuit board has copper foil on one or both sides. Therefore, even without plating, a circuit pattern can be formed directly on the copper foil, thereby forming a high-density fine circuit. In addition, when manufacturing a printed circuit board or a substrate for mounting a semiconductor component, even if plating is applied after etching the copper foil, the surface shape of the copper foil surface is transferred to the insulating resin layer, thereby improving the adhesion between the insulating resin layer and the plating.

[0239] In the manufacture of printed circuit boards, via holes and / or through holes are processed to electrically connect the conductor layers according to the needs. Hole processing is generally performed using a mechanical drill, a carbon dioxide laser, a UV laser, a YAG laser, etc. After the hole processing is performed, a roughening treatment including a desmear treatment is then performed.

[0240] Generally speaking, the roughening treatment consists of a swelling step, a surface roughening and slag dissolving step, and a neutralization step.

[0241] The swelling step is performed by swelling the surface of the insulating resin layer using a swelling agent. The swelling agent is not particularly limited as long as it can improve the wettability of the surface of the insulating resin layer and swell the surface of the insulating resin layer to the extent that it promotes oxidative decomposition in the subsequent surface roughening and smear dissolving steps. Examples thereof include alkaline solutions, surfactant solutions, and the like.

[0242] The surface roughening and smear dissolving steps are performed using an oxidant. The oxidant may be, for example, an alkaline permanganate solution, and a suitable specific example may be an aqueous potassium permanganate solution, an aqueous sodium permanganate solution, etc. The oxidant treatment is called wet desmearing, but in addition to the wet desmearing, other conventional roughening treatments such as dry desmearing by plasma treatment or UV treatment, mechanical grinding with a polishing agent, sandblasting, etc. may be appropriately combined and implemented.

[0243] The neutralization step is to neutralize the oxidizing agent used in the previous step with a reducing agent. The reducing agent may be an amine reducing agent, and suitable specific examples include acidic aqueous solutions such as hydroxylamine sulfate aqueous solution, ethylenediaminetetraacetic acid aqueous solution, and nitrilotriacetic acid aqueous solution.

[0244] In this embodiment, after providing the through hole and / or the through hole, or after desmearing the through hole and / or the through hole, it is preferable to perform metal plating treatment in order to electrically connect each conductor layer. In this embodiment, even if metal plating treatment is applied, the adhesion between the insulating resin layer and the metal plating is improved because the copper foil surface is transferred to the insulating resin layer.

[0245] The method of metal plating is not particularly limited, and a metal plating method for manufacturing a general multilayer printed circuit board can be appropriately used. The method of metal plating and the type of chemical solution used for plating are not particularly limited, and a metal plating method and chemical solution for manufacturing a general multilayer printed circuit board can be appropriately used. The chemical solution used for metal plating can also be a commercial product.

[0246] The metal plating treatment method is not particularly limited, and examples thereof include treatment with a degreasing solution, treatment with a soft etching solution, pickling, treatment with a pre-dip solution, treatment with a catalyst solution, treatment with an accelerator solution, treatment with a chemical copper solution, pickling, and immersion in a copper sulfate solution and passing an electric current.

[0247] In addition, when a semi-cured resin sheet is laminated with, for example, a copper foil with an insulating resin layer, generally, the semi-cured insulating resin layer can be completely cured by heat treatment, etc. to obtain a printed circuit board. In this embodiment, other resin sheets, for example, a copper foil with an insulating resin layer, can be further laminated on the obtained printed circuit board.

[0248] The lamination method of the build-up method is not particularly limited, and a vacuum pressurized laminator can be used appropriately. In this case, the resin sheet of this embodiment can be, for example, a copper foil with an insulating resin layer and an elastic volume layer such as rubber interposed therebetween. The lamination conditions are not particularly limited as long as they are used for lamination of general printed circuit boards, for example, at a temperature of 70°C to 140°C and 1kgf / cm2 ~11kgf / cm 2 The process is carried out under a contact pressure in a range of 20 hPa and an atmospheric pressure reduction of less than 20 hPa. After the lamination step, the laminated film may be smoothed by hot pressing with a metal plate. The lamination step and the smoothing step may be continuously performed by a commercially available vacuum pressurized lamination machine. After the lamination step or after the smoothing step, there may also be a heat curing step. By using the heat curing step, the insulating resin layer can be completely cured. The heat curing conditions vary depending on the types of components contained in the resin composition, but in general, the curing temperature is between 170°C and 220°C and the curing time is between 15 minutes and 200 minutes.

[0249] The method for forming a circuit pattern on the copper foil on one or both sides of the printed wiring board of the present embodiment includes a semi-additive method, a full-additive method, a subtractive method, etc. Among them, the semi-additive method is preferred from the viewpoint of forming a fine circuit pattern.

[0250] An example of a method for forming a circuit pattern by a semi-additive method is to use a plating resist and selectively apply electrode plating (pattern plating), then peel off the plating resist, etch the entirety in an appropriate amount, and form a circuit pattern. The circuit pattern formation by the semi-additive method is carried out by combining electroless plating and electrode plating. In this case, it is preferred to dry the electrodeless plating and the electrode plating separately. There is no particular limitation on drying after the electroless plating, and for example, it is preferred to dry at 80°C to 180°C for 10 minutes to 120 minutes. There is no particular limitation on drying after the electrode plating, and for example, it is preferred to dry at 130°C to 220°C for 10 minutes to 120 minutes. Plating is preferably copper plating.

[0251] An example of a method of forming a circuit pattern by a subtractive process is a method of forming a circuit pattern by using a resist and selectively removing a conductor layer. Specifically, for example, it can be performed as follows. On the entire surface of the copper foil, a dry film resist (RD-1225 (trade name) manufactured by Hitachi Chemical) is laminated at a temperature of 110±10°C and a pressure of 0.50±0.02MPa. Then, it is exposed along the circuit pattern and masked. Next, the dry film resist is rinsed in a 1% sodium carbonate aqueous solution, and finally the dry film resist is stripped in an amine-based resist stripping solution. In this way, a circuit pattern can be formed on the copper foil.

[0252] In this embodiment, an insulating resin layer and / or a conductor layer may be further laminated on the printed circuit board to obtain a multilayer printed circuit board. A circuit substrate may also be provided in the inner layer of the multilayer printed circuit board. The resin sheet of this embodiment, for example, a copper foil with an insulating resin layer, constitutes one of the insulating resin layer and the conductor layer of the multilayer printed circuit board.

[0253] The lamination method is not particularly limited, and a lamination molding method commonly used for general printed circuit boards can be used. Examples of the lamination method include: multi-stage pressurization, multi-stage vacuum pressurization, a laminator, a vacuum laminator, an autoclave molding machine, etc. The temperature during lamination is not particularly limited, for example, 100°C to 300°C; the pressure is not particularly limited, for example, 0.1 kgf / cm 2 ~100kgf / cm 2 (about 9.8 kPa to about 9.8 MPa); the heating time is not particularly limited, for example, it can be appropriately selected in the range of 30 seconds to 5 hours. In addition, it can also be post-cured in the temperature range of 150°C to 300°C to adjust the curing degree according to the needs.

[0254] The insulating layer of the printed circuit board of this embodiment can also use the above-mentioned prepreg. The method of laminating the prepreg of this embodiment as a build-up material is, for example, the method is: laminating the required number of prepregs of this embodiment on the metal foil and / or conductor layer on the surface of the metal foil-clad laminate, further laminating copper foil on the outside thereof, and heating and pressing to form an integral body.

[0255] According to the resin composition, resin sheet and printed circuit board of the present embodiment, since they contain: a maleimide compound (A) having an aromatic ring in the main skeleton and a relative dielectric constant of less than 2.7 at 10GHz when cured alone, a polyphenylene ether compound (B) having a number average molecular weight of 1000 or more and 7000 or less as shown in the general formula (1), and a block copolymer (C) having a styrene skeleton, excellent low dielectric constant, low dielectric loss tangent, flexibility, thin film, and reduced high-frequency signal loss can be obtained. In addition, if it is a prepreg, since it contains the resin composition of the present embodiment, excellent formability, low dielectric constant, low dielectric loss tangent, and peel strength can be obtained.

[0256] The present invention will be described in more detail below using Examples and Comparative Examples, but the present invention is not limited to these Examples.

[0257] [Example]

[0258] (Example 1)

[0259] 40 parts by mass of a maleimide compound (A) represented by general formula (6) having an aromatic ring in its main skeleton and a relative dielectric constant of less than 2.7 at 10 GHz when cured alone (MIR-5000, relative dielectric constant of 2.6 when cured alone, manufactured by Nippon Kayaku Co., Ltd.), 35 parts by mass of a polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight of 2200, vinyl equivalent: 1100 g / eq.) in which X in general formula (10) is a structural unit of general formula (11) and -(Y-О)n2- is a structural unit of general formula (14), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene ratio of 52%) were mixed and diluted with methyl ethyl ketone to a solid content of 60% to obtain a varnish. The composition of the resin composition is shown in Table 1.

[0260] The obtained varnish is applied to one side of a copper foil with a thickness of 12 μm (3EC-M2S-VLP, Mitsui Mining & Smelting Co., Ltd.) by a bar coater to obtain a copper-attached resin sheet. The obtained copper-attached resin sheet is heated and dried at 130°C for 5 minutes using a dryer (pressure-resistant and explosion-proof steam dryer, manufactured by Takasugi Manufacturing Co., Ltd.) to obtain a semi-hardened copper-attached resin sheet with a resin thickness of 30 μm. The resin surfaces of the semi-hardened copper-attached resin sheet are contact-heated to laminate two semi-hardened copper-attached resin sheets, and then the copper foil is peeled off. The process is further repeated 4 times by contact-heating the resin surfaces to laminate two upper and lower semi-hardened copper-attached resin sheets and peeling off the copper foil, thereby obtaining a semi-hardened resin sheet with a resin layer thickness of 0.3 mm. The semi-hardened resin sheet with a resin layer thickness of 0.3 mm is placed under a pressure of 25 kg / cm 2 The resin cured plate was obtained by vacuum pressing at 210°C for 150 minutes to obtain a resin layer with a thickness of 0.3 mm. The relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated using the obtained resin cured plate. The results are shown in Table 2.

[0261] In addition, the relative dielectric constant of the maleimide compound (A) was measured by diluting the maleimide compound (A) with methyl ethyl ketone to a solid content of 30% by mass, and applying the maleimide compound (A) diluted with methyl ethyl ketone to one side of a 12 μm thick copper foil (3EC-M2S-VLP, manufactured by Mitsui Mining & Smelting Co., Ltd.) in the same manner as in the preparation method of the copper-attached resin sheet shown in Example 1. The obtained copper-attached resin sheet was heated and dried at 130° C. for 5 minutes to obtain a semi-hardened copper-attached resin sheet with a resin thickness of 30 μm. The resin surfaces of the semi-hardened copper-attached resin sheet were contacted and heated to laminate two semi-hardened copper-attached resin sheets, and then the copper foil was peeled off. The resin surfaces were contacted and heated to laminate two semi-hardened copper-attached resin sheets, and then the copper foil was peeled off. The semi-hardened resin sheet with a resin layer thickness of 0.3 mm was obtained by further repeating the process 4 times. The semi-cured resin sheet with a resin layer thickness of 0.3 mm was subjected to a pressure of 25 kg / cm 2 , vacuum pressing was performed at a temperature of 210° C. for 150 minutes to prepare a resin cured plate having a resin layer thickness of 0.3 mm, and the relative dielectric constant was measured using the obtained resin cured plate.

[0262] (Example 2)

[0263] 25 parts by mass of a maleimide compound (A) represented by the general formula (6) having an aromatic ring in its main skeleton and a relative dielectric constant of less than 2.7 at 10 GHz when cured alone (MIR-5000, relative dielectric constant of 2.6 when cured alone, manufactured by Nippon Kayaku Co., Ltd.), and a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd.) in which X in the general formula (10) is a structural unit of the general formula (11) and -(Y-О)n2- is a structural unit of the general formula (14) Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.), 35 parts by mass of styrene-butadiene block copolymer (C) (TR2250, JSR Co., Ltd., styrene ratio 52%), and 15 parts by mass of 1,3-phenylenedibis(2,6-di-xylyl phosphate) (PX-200, Daihachi Chemical Industry Co., Ltd.) as a phosphorus flame retardant (E) were mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 1. Thereafter, a resin cured plate with a thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0264] (Example 3)

[0265] 15 parts by mass of a maleimide compound (A) (MIR-5000, relative dielectric constant of 2.6 when cured alone, manufactured by Nippon Kayaku Co., Ltd.) represented by general formula (6) having an aromatic ring as the main skeleton and a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, and a polymerized polyphenylene ether compound (B) (OPE-2St22) wherein X in general formula (10) is a structural unit of general formula (11) and -(Y-О)n2- is a structural unit of general formula (14) 00, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight: 2200, vinyl equivalent: 1100 g / eq.) 15 parts by mass, styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene content 52%) 25 parts by mass, 1,3-phenylenedibis(2,6-di-xylyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E) 15 parts by mass, R in the general formula (3) 501 , R 502 , R 503 , R 504 , R 505 , R 506 , R 507 , R 508 , R 509 , R 510 , R 511 and R 512 30 parts by weight of a biphenyl maleimide compound (D) (MIR-3000, a relative dielectric constant of 2.7 when cured alone, manufactured by Nippon Kayaku Co., Ltd.) in which the hydrogen atom is present and the average value of n5 is 1.4 was mixed, and diluted with methyl ethyl ketone to a solid content of 60% by weight to obtain a varnish. The composition of the resin composition is shown in Table 1. Thereafter, a resin cured plate having a thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0266] (Example 4)

[0267] A maleimide compound (A) represented by the general formula (27) having an aromatic ring as the main skeleton and a relative dielectric constant of less than 2.7 at 10 GHz when cured alone (X9-450, relative dielectric constant of 2.4 when cured alone, manufactured by DIC Corporation) 40 parts by mass, a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight of 2200, vinyl equivalent: 1100 g / eq.) in which X in the general formula (10) is a structural unit of the general formula (11) and -(Y-О)n2- is a structural unit of the general formula (14) 35 parts by mass, and a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio of 52%) 25 parts by mass were mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 3. Thereafter, a 0.3 mm thick resin cured plate was prepared in the same manner as in Example 1, and relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0268] (Example 5)

[0269] 25 parts by mass of a maleimide compound (A) (X9-450, relative dielectric constant of 2.4 when cured alone, manufactured by DIC Corporation) represented by the general formula (27) having an aromatic ring as the main skeleton and a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, and a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd.) wherein X in the general formula (10) is a structural unit of the general formula (11) and -(Y-О)n2- is a structural unit of the general formula (14); The mixture was mixed with 35 parts by mass of styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) (25 parts by mass of styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene ratio 52%), and 15 parts by mass of 1,3-phenylenedibis(2,6-di-xylyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as a phosphorus flame retardant (E), and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 3. Thereafter, a resin cured plate with a thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0270] (Example 6)

[0271] 15 parts by mass of a maleimide compound (A) (X9-450, relative dielectric constant of 2.4 when cured alone, manufactured by DIC Corporation) represented by the general formula (27) having an aromatic ring as the main skeleton and a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, and a polymerized polyphenylene ether compound (B) (OPE-2St220) wherein X in the general formula (10) is a structural unit of the general formula (11) and -(Y-О)n2- is a structural unit of the general formula (14) 0, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight: 2200, vinyl equivalent: 1100 g / eq.) 15 parts by mass, styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene content 52%) 25 parts by mass, 1,3-phenylenedibis(2,6-di-xylyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E) 15 parts by mass, R in the general formula (3) 501 , R 502 , R 503 , R 504 , R 505 , R 506 , R 507 , R 508 , R 509 , R 510 , R 511 and R 512 The mixture was mixed with 30 parts by weight of a biphenyl maleimide compound (D) (MIR-3000, a relative dielectric constant of 2.7 when cured alone, manufactured by Nippon Kayaku Co., Ltd.) having a hydrogen atom and an average value of n5 of 1.4, and diluted with methyl ethyl ketone to a solid content of 60% by weight to obtain a varnish. The composition of the resin composition is shown in Table 3. Thereafter, a resin cured plate having a thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0272] (Example 7)

[0273] 15 parts by mass of a maleimide compound (A) (X9-450, relative dielectric constant of 2.4 when cured alone, manufactured by DIC Corporation) represented by the general formula (27) having an aromatic ring as the main skeleton and a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, and a polymerized polyphenylene ether compound (B) (OPE-2St220) wherein X in the general formula (10) is a structural unit of the general formula (11) and -(Y-О)n2- is a structural unit of the general formula (14) 0, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight: 2200, vinyl equivalent: 1100 g / eq.) 15 parts by mass, styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene content 52%) 25 parts by mass, 1,3-phenylenedibis(2,6-di-xylyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E) 15 parts by mass, R in the general formula (3) 501 , R 502 , R 503 , R 504 , R 505 , R 506 , R 507 , R 508 , R 509 , R 510 , R 511 and R 512 29 parts by mass of a biphenyl maleimide compound (D) (MIR-3000, a relative dielectric constant of 2.7 when cured alone, manufactured by Nippon Kayaku Co., Ltd.) in which the hydrogen atom is present and the average value of n5 is 1.4, and 1 part by mass of a cyanate compound (SNCN) (F) obtained in the following Synthesis Example 1 are mixed, and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 3. Thereafter, a resin cured plate with a thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0274] (Synthesis Example 1) Synthesis of Cyanate Ester Compound

[0275] 300 g (1.28 mol in terms of OH group) of 1-naphthol aralkyl resin (manufactured by Nippon Steel & Sumigin Chemical Co., Ltd.) and 194.6 g (1.92 mol) of triethylamine (1.5 mol per 1 mol of hydroxyl group) were dissolved in 1800 g of dichloromethane. This was referred to as Solution 1.

[0276] 125.9 g (2.05 mol) of cyanogen chloride (1.6 mol per mol of hydroxyl group), 293.8 g of dichloromethane, 194.5 g (1.92 mol) of 36% hydrochloric acid (1.5 mol per mol of hydroxyl group), and 1205.9 g of water were added to solution 1 over 30 minutes while stirring and maintaining the liquid temperature at -2°C to -0.5°C. After the addition of solution 1, stirring was performed at the same temperature for 30 minutes, and then a solution (solution 2) in which 65 g (0.64 mol) of triethylamine (0.5 mol per mol of hydroxyl group) was dissolved in 65 g of dichloromethane was added over 10 minutes. After the addition of solution 2, stirring was performed at the same temperature for 30 minutes to complete the reaction.

[0277] The reaction solution was then allowed to stand to separate the organic phase and the aqueous phase. The obtained organic phase was washed five times with 1300 g of water. The electrical conductivity of the waste water from the fifth washing was 5 μS / cm, and it was confirmed that the removable ionic compounds were sufficiently removed by washing with water.

[0278] The organic phase after washing was concentrated under reduced pressure and finally concentrated to dryness at 90°C for 1 hour to obtain 331 g of the target naphthol aralkyl cyanate compound (SNCN) (orange viscous substance). The mass average molecular weight Mw of the obtained SNCN was 600. In addition, the IR spectrum of SNCN showed 2250 cm -1 The absorption of the cyanate group is not shown, and the absorption of the hydroxyl group is not shown.

[0279] (Example 8)

[0280] 15 parts by mass of a maleimide compound (A) (X9-470, relative dielectric constant of 2.4 when cured alone, manufactured by DIC Corporation) represented by general formula (27) having an aromatic ring as the main skeleton and a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, and a polymerized polyphenylene ether compound (B) (OPE-2St220) wherein X in general formula (10) is a structural unit of general formula (11) and -(Y-О)n2- is a structural unit of general formula (14) 0, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight: 2200, vinyl equivalent: 1100 g / eq.) 15 parts by mass, styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene content 52%) 25 parts by mass, 1,3-phenylenedibis(2,6-di-xylyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E) 15 parts by mass, R in the general formula (3) 501 , R 502 , R 503 , R 504 , R 505 , R 506 , R 507 , R508 , R 509 , R 510 , R 511 and R 512 29 parts by mass of a biphenyl maleimide compound (D) (MIR-3000, a relative dielectric constant of 2.7 when cured alone, manufactured by Nippon Kayaku Co., Ltd.) in which the hydrogen atom is present and the average value of n5 is 1.4, and 1 part by mass of a cyanate compound (SNCN) (F) obtained in Synthesis Example 1 shown in Example 7 are mixed, and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 3. Thereafter, a resin cured plate with a thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0281] (Example 9)

[0282] A maleimide compound (A) represented by the general formula (27) having an aromatic ring as the main skeleton and a relative dielectric constant of less than 2.7 at 10 GHz when cured alone (X9-470, relative dielectric constant of 2.4 when cured alone, manufactured by DIC Corporation) 40 parts by mass, a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) in which X in the general formula (10) is a structural unit of the general formula (11) and -(Y-О)n2- is a structural unit of the general formula (14) 35 parts by mass, and a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%) 25 parts by mass were mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 3. Thereafter, a 0.3 mm thick resin cured plate was prepared in the same manner as in Example 1, and relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0283] (Comparative Example 1)

[0284] In general formula (3), R 501 , R 502 , R 503 , R 504 , R 505 , R 506 , R 507 , R 508 , R 509 , R 510 , R 511 and R 512A biphenyl maleimide compound (D) (MIR-3000, relative dielectric constant of 2.7 when cured alone, manufactured by Nippon Kayaku Co., Ltd.) in which X in general formula (10) is a structural unit of general formula (11) and -(Y-О)n2- is a structural unit of general formula (14) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) 35 parts by mass, and a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene ratio 52%) 25 parts by mass were mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 1. Thereafter, a 0.3 mm thick resin cured plate was prepared in the same manner as in Example 1, and relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0285] (Comparative Example 2)

[0286] 50 parts by mass of a maleimide compound (A) (MIR-5000, a relative dielectric constant of 2.6 when cured alone, manufactured by Nippon Kayaku Co., Ltd.) having an aromatic ring as the main skeleton and a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, and 50 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene ratio 52%) are mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 1. Thereafter, a resin cured plate with a thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0287] (Comparative Example 3)

[0288] A maleimide compound (A) (MIR-5000, relative dielectric constant of 2.6 when cured alone, manufactured by Nippon Kayaku Co., Ltd.) having an aromatic ring as the main skeleton and a relative dielectric constant of less than 2.7 at 10 GHz when cured alone was 50 parts by mass and a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight of 2200, vinyl equivalent: 1100 g / eq.) having a structural unit in which X in general formula (10) is general formula (11) and -(Y-О)n2- is general formula (14) were mixed, and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 1. Subsequently, a resin cured plate with a thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. Table 2 shows the evaluation results of the obtained resin cured plates.

[0289] (Comparative Example 4)

[0290] 50 parts by mass of a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) in which X in general formula (10) is a structural unit of general formula (11) and -(Y-О)n2- is a structural unit of general formula (14) and 50 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene content 52%) are mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 1. Subsequently, a resin cured plate with a thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0291] (Comparative Example 5)

[0292] 40 parts by mass of a maleimide compound (D) represented by the following general formula (16) (BMI-70, relative dielectric constant of 3.2 when cured alone, manufactured by KI Chemical Co., Ltd.), 35 parts by mass of a polymerized polyphenylene ether compound (B) wherein X in the general formula (10) is a structural unit of the general formula (11) and -(Y-О)n2- is a structural unit of the general formula (14) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene content 52%) were mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 1. Thereafter, a 0.3 mm thick resin cured plate was prepared in the same manner as in Example 1, and relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0293] [Chemistry 30]

[0294]

[0295] In addition, the maleimide compound (D) represented by the general formula (16) is, in the general formula (4), R 61 , R 63 is methyl, R 62 , R 64 is ethyl, R 71 , R 72 It's a hydrogen atom.

[0296] [Table 1]

[0297]

[0298] [Table 2]

[0299]

[0300] [Table 3]

[0301]

[0302] (Measurement Method and Evaluation Method of Examples 1 to 9 and Comparative Examples 1 to 5)

[0303] (1) Relative dielectric constant (Dk) and relative dielectric loss tangent (Df):

[0304] Using samples obtained by removing the copper foil of the resin-cured plates obtained in each Example and each Comparative Example, relative dielectric constant and relative dielectric loss tangent at 10 GHz were measured using a perturbation cavity resonator (CP-531, manufactured by Kanto Denshi Applied Development Co., Ltd.).

[0305] (2) Copper foil peel strength:

[0306] The resin cured plates obtained in the examples and comparative examples were tested for peel strength of the copper foil using 12 μm copper foil test pieces (30 mm×150 mm×0.3 mm) in accordance with JIS C6481, and the average value of the lower limit values ​​was taken as the measured value.

[0307] (3) Uniformity of hardened material:

[0308] The cross section of the resin cured plate obtained in each example and each comparative example was polished by MetaServ 3000 manufactured by Buehler, and the state of the cross section was observed using EPIPHOT manufactured by Nikon. The plate was rated NG if voids and poor dispersion were observed, and rated OK if no voids or poor dispersion were observed.

[0309] (4) Evaluation of flexibility:

[0310] The semi-cured copper-coated resin sheets with a resin thickness of 30 μm obtained in each of the examples and comparative examples were subjected to a cylindrical mandrel bending test in accordance with JIS K5600-5-1, and the diameter of the mandrel at which the first resin crack occurred was recorded.

[0311] (Results of Examples 1 to 9 and Comparative Examples 1 to 5)

[0312] As shown in Table 2, in Comparative Examples 1 and 5 in which the maleimide compound (A) is replaced and mixed with the maleimide compound (D), the relative dielectric constant and relative dielectric loss tangent are higher than those of the present embodiment. In Comparative Example 2 in which the polyphenylene ether compound (B) is not mixed, the uniformity of the cured product is poor, and the peel strength is smaller than that of the present embodiment. In Comparative Example 3 in which the styrene-butadiene block copolymer (C) is not mixed, the flexibility is worse than that of the present embodiment, and the peel strength is smaller than that of the present embodiment. In Comparative Example 4 in which the maleimide compound (A) and the maleimide compound (D) are not mixed, although the relative dielectric constant is low, the peel strength is lower than that of the present embodiment.

[0313] That is, it has been confirmed that by using the resin composition of the present invention, excellent low dielectric constant, low dielectric loss tangent, peel strength, and flexibility can be obtained, and a uniform cured product can be obtained.

[0314] (Example 10)

[0315] 40 parts by mass of a maleimide compound (A) (MIR-5000, manufactured by Nippon Kayaku Co., Ltd.) represented by general formula (6), 35 parts by mass of a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) wherein X in general formula (10) is a structural unit of general formula (11) and -(Y-О)n2- is a structural unit of general formula (14), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene ratio 52%) were mixed and dissolved in methyl ethyl ketone to obtain a varnish. The varnish was dip-coated on an E glass fiber substrate and dried by heating at 165°C for 3 minutes to obtain a prepreg having a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 4.

[0316] (Example 11)

[0317] 25 parts by mass of a maleimide compound (A) represented by the general formula (6) (MIR-5000, manufactured by Nippon Kayaku Co., Ltd.), 35 parts by mass of a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) wherein X in the general formula (10) is a structural unit of the general formula (11) and -(Y-О)n2- is a structural unit of the general formula (14), 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene content 52%), and 15 parts by mass of 1,3-phenylenedibis(2,6-di-xylyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E) are mixed and dissolved in methyl ethyl ketone to obtain a varnish. The varnish was dip-coated on an E glass fiber substrate and dried by heating at 165° C. for 3 minutes to obtain a prepreg having a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 4.

[0318] (Example 12)

[0319] 15 parts by mass of a maleimide compound (A) represented by the general formula (6) (MIR-5000, manufactured by Nippon Kayaku Co., Ltd.), 15 parts by mass of a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) wherein X in the general formula (10) is a structural unit of the general formula (11) and -(Y-О)n2- is a structural unit of the general formula (14), 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene content 52%), 15 parts by mass of 1,3-phenylenedibis(2,6-di-xylyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E), and 15 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene content 52%). 501 , R 502 , R 503 , R 504 , R 505 , R 506 , R 507 , R 508 , R 509 , R 510 , R 511 , R 512 30 parts by mass of a biphenyl maleimide compound (D) (MIR-3000, manufactured by Nippon Kayaku Co., Ltd.) having a hydrogen atom and an average n5 value of 1.4 were mixed and dissolved in methyl ethyl ketone to obtain a varnish. The varnish was dip-coated on an E glass fiber substrate and heated and dried at 165° C. for 3 minutes to obtain a prepreg having a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 4.

[0320] (Example 13)

[0321] 40 parts by mass of a maleimide compound (A) (X9-450, manufactured by DIC Corporation) represented by general formula (27), 35 parts by mass of a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) wherein X in general formula (10) is a structural unit of general formula (11) and -(Y-О)n2- is a structural unit of general formula (14), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene content 52%) were mixed and dissolved in methyl ethyl ketone to obtain a varnish. The varnish was dip-coated on an E glass fiber substrate and heated and dried at 165°C for 3 minutes to obtain a prepreg having a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 6.

[0322] (Example 14)

[0323] 25 parts by mass of a maleimide compound (A) (X9-450, manufactured by DIC Corporation) represented by general formula (27), 35 parts by mass of a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) wherein X in general formula (10) is a structural unit of general formula (11) and -(Y-О)n2- is a structural unit of general formula (14), 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene content 52%), and 15 parts by mass of 1,3-phenylenedibis(2,6-di-xylyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E) are mixed and dissolved in methyl ethyl ketone to obtain a varnish. The varnish was dip-coated on an E glass fiber substrate and dried by heating at 165° C. for 3 minutes to obtain a prepreg having a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 6.

[0324] (Example 15)

[0325] 15 parts by mass of a maleimide compound (A) (X9-450, manufactured by DIC Corporation) represented by the general formula (27), 15 parts by mass of a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) wherein X in the general formula (10) is a structural unit of the general formula (11) and -(Y-О)n2- is a structural unit of the general formula (14), 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene content 52%), 15 parts by mass of 1,3-phenylenedibis(2,6-di-xylyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E), and 15 parts by mass of R in the general formula (3) 501 , R 502 , R 503 , R 504 , R 505 , R 506 , R 507 , R 508 , R 509 , R 510 , R 511 and R 512 30 parts by mass of a biphenyl maleimide compound (D) (MIR-3000, manufactured by Nippon Kayaku Co., Ltd.) having a hydrogen atom and an average n5 value of 1.4 were mixed and dissolved in methyl ethyl ketone to obtain a varnish. The varnish was dip-coated on an E glass fiber substrate and heated and dried at 165° C. for 3 minutes to obtain a prepreg having a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 6.

[0326] (Example 16)

[0327] 40 parts by mass of a maleimide compound (A) (X9-470, manufactured by DIC Corporation) represented by general formula (27), 35 parts by mass of a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) wherein X in general formula (10) is a structural unit of general formula (11) and -(Y-О)n2- is a structural unit of general formula (14), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene content 52%) were mixed and dissolved in methyl ethyl ketone to obtain a varnish. The varnish was dip-coated on an E glass fiber substrate and dried by heating at 165°C for 3 minutes to obtain a prepreg having a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 6.

[0328] (Example 17)

[0329] 15 parts by mass of a maleimide compound (A) (X9-450, manufactured by DIC Corporation) represented by the general formula (27), 15 parts by mass of a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) wherein X in the general formula (10) is a structural unit of the general formula (11) and -(Y-О)n2- is a structural unit of the general formula (14), 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene content 52%), 15 parts by mass of 1,3-phenylenedibis(2,6-di-xylyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E), and 15 parts by mass of R in the general formula (3) 501 , R 502 , R 503 , R 504 , R 505 , R 506 , R 507 , R 508 , R 509 , R 510 , R 511 and R 51229 parts by mass of a biphenyl maleimide compound (D) (MIR-3000, manufactured by Nippon Kayaku Co., Ltd.) having a hydrogen atom and an average value of n5 of 1.4 and 1 part by mass of a cyanate compound (SNCN) (F) obtained by Synthesis Example 1 described in Example 7 were mixed and dissolved in methyl ethyl ketone to obtain a varnish. The varnish was dip-coated on an E glass fiber substrate and heated and dried at 165° C. for 3 minutes to obtain a prepreg having a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 6.

[0330] (Example 18)

[0331] 15 parts by mass of a maleimide compound (A) (X9-470, manufactured by DIC Corporation) represented by the general formula (27), 15 parts by mass of a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) wherein X in the general formula (10) is a structural unit of the general formula (11) and -(Y-О)n2- is a structural unit of the general formula (14), 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene content 52%), 15 parts by mass of 1,3-phenylenedibis(2,6-di-xylyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E), and 15 parts by mass of R in the general formula (3) 501 , R 502 , R 503 , R 504 , R 505 , R 506 , R 507 , R 508 , R 509 , R 510 , R 511 and R 512 29 parts by mass of a biphenyl maleimide compound (D) (MIR-3000, manufactured by Nippon Kayaku Co., Ltd.) having a hydrogen atom and an average value of n5 of 1.4 and 1 part by mass of a cyanate compound (SNCN) (F) obtained by Synthesis Example 1 described in Example 8 were mixed and dissolved in methyl ethyl ketone to obtain a varnish. The varnish was dip-coated on an E glass fiber substrate and heated and dried at 165° C. for 3 minutes to obtain a prepreg having a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 6.

[0332] (Comparative Example 6)

[0333] 50 parts by mass of a maleimide compound (A) (MIR-5000, manufactured by Nippon Kayaku Co., Ltd.) and 50 parts by mass of a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) in which X in general formula (10) is general formula (11) and -(Y-О)n2- is structural unit of general formula (14) were mixed, and the varnish was dip-coated on an E glass fiber substrate and heated and dried at 165° C. for 3 minutes to obtain a prepreg having a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 4.

[0334] (Comparative Example 7)

[0335] 50 parts by mass of maleimide compound (A) (MIR-5000, manufactured by Nippon Kayaku Co., Ltd.) and 50 parts by mass of styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene ratio 52%) were mixed, and the varnish was dip-coated on an E glass fiber substrate, and heated and dried at 165° C. for 3 minutes to obtain a prepreg having a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 4.

[0336] (Comparative Example 8)

[0337] A polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) in which X in general formula (10) is a structural unit of general formula (11) and -(Y-О)n2- is a structural unit of general formula (14) was mixed with 50 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene ratio 52%), and the varnish was dip-coated on an E glass fiber substrate, and heated and dried at 165° C. for 3 minutes to obtain a prepreg having a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 4.

[0338] (Comparative Example 9)

[0339] 40 parts by mass of the maleimide compound (D) (BMI-70, manufactured by KI Chemical Co., Ltd.) represented by the general formula (16) used in Comparative Example 5, 35 parts by mass of a polymerized polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl equivalent: 1100 g / eq.) wherein X in the general formula (10) is the structural unit of the general formula (11) and -(Y-О)n2- is the structural unit of the general formula (14), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene ratio 52%) were mixed and dissolved in methyl ethyl ketone to obtain a varnish. The varnish was dip-coated on an E glass fiber substrate and dried by heating at 165°C for 3 minutes to obtain a prepreg having a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 4.

[0340] (Preparation of samples for evaluation of Examples 10 to 18 and Comparative Examples 6 to 9)

[0341] The prepregs obtained in Examples 10 to 18 and Comparative Examples 6 to 9 were stacked 8 sheets for each Example and Comparative Example, and copper foil (3EC-M3-VLP, manufactured by Mitsui Mining & Smelting Co., Ltd., thickness 12 μm) was placed on both the upper and lower surfaces, and the prepregs were pressed under a pressure of 5 kgf / cm 2 , and laminate forming (thermal curing) was performed at a temperature of 230°C for 100 minutes to obtain a copper-clad laminate with an insulating layer thickness of about 0.8 mm.

[0342] (Evaluation of Formability of Examples 10 to 18 and Comparative Examples 6 to 9)

[0343] The copper-clad laminates obtained in each embodiment and each comparative example were removed by etching, and those with pores and poor dispersion observed on the surface and cross-section were NG, and those without pores were OK. The results are shown in Table 5. In addition, pores refer to the presence of voids without the presence of glass fibers and cured resin.

[0344] (Evaluation of relative dielectric constant and relative dielectric loss tangent ratio of Examples 10 to 18 and Comparative Examples 6 to 9)

[0345] The copper-clad laminate obtained in each embodiment and each comparative example was cut into a size of 100 mm × 1.0 mm with a dicing saw, and the copper foil on the surface was removed by etching to obtain a sample for measurement. The relative dielectric constant and relative dielectric loss tangent at 10 GHz were measured using this sample by a perturbation method resonant cavity device (Kanto Electronics Application Development Co., Ltd. product, CP-531). The measurement results obtained are shown in Table 5.

[0346] (Evaluation of Peel Strength of Examples 10 to 18 and Comparative Examples 6 to 9)

[0347] The copper-clad laminates obtained in each example and each comparative example were cut into a size of 150 mm×30 mm with a dicing saw, and then the peel strength of the copper foil was measured in Test 3 according to JIS C6481, and the average value of the lower limit values ​​was taken as the measured value.

[0348] [Table 4]

[0349]

[0350] [Table 5]

[0351]

[0352] [Table 6]

[0353]

[0354] As shown in Tables 4 to 6, in the resin compositions impregnated or coated on the glass fiber substrate described in Examples 10 to 18, the prepreg containing a maleimide compound (A) having an aromatic ring as the main skeleton, a polyphenylene ether compound (B), and a block copolymer (C) having a styrene skeleton, or containing a maleimide compound (A), a polyphenylene ether compound (B), a block copolymer (C) having a styrene skeleton, and a maleimide compound (D) has been confirmed to have no molding defects when the laminated material is obtained by thermal curing, and has a relative dielectric constant of less than 3.5, a relative dielectric loss tangent of less than 0.0043, and a peel strength of 0.6 kN / m.

[0355] In contrast, in the resin composition impregnated or coated on a glass fiber substrate described in Comparative Example 6, the prepreg containing a maleimide compound (A) having an aromatic ring as the main skeleton and a polyphenylene ether compound (B) has been confirmed to have a relative dielectric constant and relative dielectric loss tangent of the laminated material obtained by thermal curing that are higher than those of the present embodiment, and a lower peel strength than those of the present embodiment.

[0356] In the resin composition impregnated or coated on the glass fiber substrate described in Comparative Example 7, the prepreg containing a maleimide compound (A) having an aromatic ring as the main skeleton and a block copolymer (C) having a styrene skeleton was confirmed to have poor molding of the laminated material obtained by thermal curing, and the relative dielectric constant, relative dielectric loss tangent, and peel strength could not be measured.

[0357] In the resin composition impregnated or coated on the glass fiber substrate described in Comparative Example 8, the prepreg containing a polyphenylene ether compound (B) and a block copolymer (C) having a styrene skeleton was confirmed to have poor molding of the laminated material obtained by thermal curing, and the relative dielectric constant, relative dielectric loss tangent, and peel strength could not be measured.

[0358] In the resin composition impregnated or coated on the glass fiber substrate described in Comparative Example 9, the prepreg containing a maleimide compound (D) having an aromatic ring as the main skeleton, a polyphenylene ether compound (B), and a block copolymer (C) having a styrene skeleton, it has been confirmed that the relative dielectric constant and relative dielectric loss tangent of the laminated material obtained by thermal curing are higher than those of the present embodiment.

[0359] That is, it was confirmed that according to this embodiment, excellent moldability, low dielectric constant characteristics, low dielectric loss tangent, and peel strength can be obtained.

[0360] [Industrial Applicability]

[0361] As described above, the resin composition of the present invention can be widely and effectively used in various applications such as electrical / electronic materials, mechanical engineering materials, and aviation materials, for example, electrical insulating materials, semiconductor plastic packaging, sealing materials, adhesives, laminate materials, anti-corrosion agents, build-up laminate materials, etc., and can be particularly effectively used as a printed circuit board material corresponding to the high integration and high density of information terminal equipment or communication equipment in recent years.

Claims

1. A resin composition, characterized in that it contains: A maleimide compound (A) having an aromatic ring as the main skeleton and a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, a polyphenylene ether compound (B) having a number average molecular weight of 1000 to 7000 represented by the following general formula (1), and a block copolymer (C) having a styrene skeleton; [Chemistry 1] In the above general formula (1), X represents an aryl group, -(Y-O)n2- represents a polyphenylene ether moiety, R1, R2 and R3 each independently represent a hydrogen atom, an alkyl group, an alkenyl group or an alkynyl group, n2 represents an integer of 1 to 100, n1 represents an integer of 1 to 6, and n3 represents an integer of 1 to 4. The maleimide compound (A) is at least one selected from the group consisting of compounds represented by the following general formula (22), and contains at least one compound other than the compound wherein nx is 0 in the following general formula (22). [Chemistry 3] In the above general formula (22), R M1 , R M2 , R M3 and R M4 Each independently represents a hydrogen atom or an organic group; R M5 and R M6 Each independently represents a hydrogen atom or an alkyl group; Ar M represents a divalent aromatic group; A is a 4- to 6-membered alicyclic group; R M7 and R M8 Each is independently an alkyl group; mx is 1 or 2, lx is 0 or 1; R M9 and R M10 Each independently represents a hydrogen atom or an alkyl group; R M11 , R M12 , R M13 and R M14 Each independently represents a hydrogen atom or an organic group; and nx represents an integer of 0 to 20.

2. The resin composition according to claim 1, wherein The block copolymer (C) having a styrene skeleton contains at least one selected from the group consisting of styrene-butadiene block copolymers, styrene-isoprene block copolymers, styrene-hydrogenated butadiene block copolymers, styrene-hydrogenated isoprene copolymers and styrene-hydrogenated (isoprene / butadiene) copolymers.

3. The resin composition according to claim 1, wherein Furthermore, a maleimide compound (D) other than the maleimide compound (A) is contained.

4. The resin composition according to claim 3, wherein The maleimide compound (D) comprises at least one selected from the group consisting of the following general formulas (2), (3), (4) and (5); [Chemistry 4] In the above general formula (2), R 41 and R 42 Each independently represents a hydrogen atom or a methyl group, and n4 represents an integer greater than 1; [Chemistry 5] In the above general formula (3), R 501 , R 502 , R 503 , R 504 , R 505 , R 506 , R 507 , R 508 , R 509 , R 510 , R 511 and R 512 Each independently represents a hydrogen atom, an alkyl group having 1 to 8 carbon atoms, or a phenyl group, and n5 represents an integer of 1 to 10; [Chemistry 6] In the above general formula (4), R 61 , R 62 , R 63 and R 64 Each independently represents a hydrogen atom, a methyl group or an ethyl group, and R 71 and R 72 each independently represents a hydrogen atom or a methyl group; [Chemistry 7] In the above general formula (5), R 81 and R 82 Each independently represents a hydrogen atom, a methyl group or an ethyl group.

5. The resin composition according to claim 1, wherein It further contains a flame retardant (E).

6. The resin composition according to claim 1, wherein It further contains a cyanate compound (F).

7. A resin sheet, characterized in that The invention comprises: a support, and a layer formed of the resin composition according to claim 1 and arranged on a surface of the support.

8. A prepreg, characterized in that The invention comprises: a substrate, and the resin composition as claimed in claim 1 which is impregnated or coated on the substrate.

9. A printed circuit board comprising an insulating layer and a conductor layer disposed on a surface of the insulating layer, wherein: The insulating layer comprises a layer formed of the resin composition according to claim 1 .

Citation Information

Patent Citations

  • Resin composition, prepreg, metal foil-clad laminate, resin sheet and printed wiring board

    WO2019230945A1

  • Resin composition and applications thereof

    WO2020004211A1